Curable polymer compositions with improved washing resistance
By preparing a curable polymer composition containing ethylene polymer, tackifier, curing agent and rheology modifier, the problem that existing adhesives cannot be pumped at low temperatures and are easy to wash off at medium temperatures, achieving more efficient bonding effect and more stable quality in the automobile manufacturing process.
Patent Information
- Application Number
- CN202380063549.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-14
- Filing Date
- 2023-09-04
- Publication Date
- 2025-04-15
AI Technical Summary
The existing curable and pumpable adhesives are not pumpable at low temperatures and are easily washed off at medium temperatures, resulting in unstable adhesives during automobile manufacturing, affecting manufacturing efficiency and quality.
By combining appropriate ethylene polymers, tackifiers, curing agents and rheology modifiers, a curable polymer composition that can be pumpable at low temperatures is prepared and maintains wash-off resistance at medium temperatures. The composition can be extruded to the substrate surface by a robot mounted extrusion die and activated by external stimulation to cure.
The pumpable characteristics are achieved at low temperatures while maintaining wash-off resistance at medium temperatures, avoiding precuring steps, improving manufacturing efficiency and reducing energy consumption.
Smart Images

Figure BDA0005295752660000341
Abstract
Description
[0001] Claiming priority from European patent application No. 22193932.5 filed on September 5, 2022 and from European patent application No. 23161799.4 filed on March 14, 2023. Technical Field
[0002] The present invention relates to a curable and preferably pumpable polymer composition used as a sealant, adhesive (e.g., structural adhesive), reinforcing agent, damping material, sound absorbing material or any combination thereof. The composition preferably comprises one or more ethylene polymers, a tackifier, a curing agent and a rheology modifier. The present invention also relates to extruding the composition onto the surface of an article, for example, by a robotically mounted extrusion die, and subsequently activating to cure by an external stimulus. The composition is particularly suitable for application by in-situ extrusion. Background Art
[0003] In conventional automobile manufacturing process, in the first step, for example, by the method of robot (robot), optionally under the intermediate temperature (extrusion temperature) that is not enough to cause solidification, curable and pumpable adhesive is applied to the surface of the substrate of vehicle with its uncured state. In the second step, substrate can be assembled with opposite substrate and mechanically fastened or welded along bonding line to lock two substrates in place. Then curable and pumpable adhesive is positioned between the substrate and opposite substrate to which it has been applied as film or strip etc. In the third step, for cleaning purposes, i.e., removing oil and / or dirt, and / or for anti-corrosion purposes, i.e., applying suitable anti-corrosion coating (electrophoretic coating (e-coat)), the body with mechanically fastened or welded substrate is subjected to a series of spraying (sprays) and bathing (baths). In the fourth step, the body so treated and coated is subjected to the high temperature (curing temperature) causing the solidification of adhesive in an oven so that two substrates are bonded to each other.
[0004] Therefore, curable and pumpable adhesives need to meet certain requirements about rheology at different temperatures and also about wash-off resistance. At low temperatures, curable and pumpable adhesives should have good pumpability. At intermediate temperatures, curable and pumpable adhesives should have appropriate rheology to prevent washing but should not be cured prematurely. In its uncured state, curable and pumpable adhesives need to withstand intermediate temperatures without curing, and withstand subsequent exposure to large amounts of water and other liquids during the third step. If the curable and pumpable adhesive fails to withstand the above conditions, it will be washed off from the body during the third step. The washed-off material not only contaminates the bath, but is often re-deposited on the surface of the body in different areas, which is undesirable, for example, because this can cause coating defects. At high temperatures, curable and pumpable adhesives (before and during its application to the article, such as before curing, can be regarded as thermoplastic materials) should be cured, thereby becoming thermosetting materials.
[0005] Such a rheological curve is difficult to achieve because the viscosity of most liquids is strongly dependent on temperature and generally increases exponentially with decreasing temperature (Andrade equation, μ = Ae B / T ).
[0006] Since several conventional curable and pumpable adhesives fail the wash-off test, it has been suggested to improve the wash-off resistance by means of a pre-curing step, which is usually achieved by heating the assembly at a temperature of about 160° C. for about 15 minutes before the assembly is subjected to the spraying and coating steps (i.e., exposed to the liquid). Pre-curing does not ultimately cure the adhesive, but it improves the wash-off resistance by causing an increase in viscosity due to partial curing. However, such pre-curing is disadvantageous because it requires additional processing steps, prolongs the time of manufacture, and consumes additional energy. In addition, it is difficult to control the degree of curing because the material should maintain residual curability when it is finally exposed to the high temperature (curing temperature) again. In addition, when the material is expandable, it is difficult to avoid premature volume expansion during the pre-curing (activation temperature). Therefore, it is desirable to provide a curable and pumpable adhesive that passes the wash-off test without the need for prior pre-curing.
[0007] A further problem arises when the surface of a substrate (e.g., a metal and / or polymer sheet or other article (e.g., a carrier for a baffle and / or structural reinforcement) to which a curable and pumpable adhesive is applied is oily or contains some other surface contaminant. Oil or other contaminants may have a negative impact on the adhesion of the uncured adhesive and thus deteriorate its wash-off resistance. Therefore, it is desirable to provide a curable and pumpable adhesive that can withstand oily or other contaminated surfaces while maintaining wash-off resistance and also provide satisfactory adhesion after curing. Some conventional curable and pumpable adhesives only provide satisfactory adhesion to oily or other contaminated surfaces of the substrate when the substrate is heated to a temperature (substrate temperature) that is typically greater than 70°C. It is desirable to provide a curable and pumpable adhesive that provides satisfactory adhesion to oily or other contaminated surfaces of a substrate (e.g., a metal and / or polymer sheet) without the need to heat the substrate, or only requires the substrate to be heated to a lower temperature (substrate temperature), for example, less than 55°C. It is desirable to provide a curable and pumpable adhesive that provides satisfactory adhesion to oily or otherwise contaminated surfaces of substrates in a process without any surface treatment steps to the substrate (e.g., the process does not include any steps such as plasma treatment, flame spraying, heating above 55°C, etc.).
[0008] When the substrate that has been applied with curable and pumpable adhesive is not assembled with the opposite substrate before undergoing a series of spraying and bathing, specific problems may occur.In these cases, the curable and pumpable adhesive applied is not subject to the protection (that is, at the interface between substrate and the opposite substrate) of sandwich assembly (assembly), but one side is fully exposed to the bathing liquid due to lacking the opposite substrate.The situation lacking the opposite substrate is related to the manufacture of vehicles such as when the curable and pumpable adhesive volume expansion is to fill the cavity when heating activation.Then curable and pumpable adhesive is applied to the inner surface of the substrate that forms / surrounds the cavity, but the opposite substrate is not applied thereon.Once assembly is subjected to high temperature (curing temperature), curable and pumpable adhesive solidifies and expands its volume (activation temperature) simultaneously thereby filling the cavity.As a result of volume expansion, the adhesive material contacts and bonds with the opposite side of the cavity. However, in the intermediate state, i.e. before any expansion and / or solidification, when the assembly is subjected to the corresponding processing steps, the curable and pumpable adhesive applied is completely exposed to the bathing liquid. Other related applications with or without the opposing substrate (and the subject matter of this teaching is related to) include but are not limited to the lower or upper outer section of the A column, the lower or upper outer section of the B column, the lower or upper outer section of the C column, the lower or upper outer section of the D column, the track, the top bow, the crossbeam, the battery support, the battery frame, the reinforcement and / or the baffle and another vehicle component (e.g., skin, door or other closure, vehicle top, engine hood, floor, truck compartment and luggage box) One or more joints. For the above, under some conditions, such as under the condition of lacking the opposing substrate, it is obviously more difficult to achieve wash-off resistance.
[0009] EP1331080A2 relates to a method for applying a molten flowable material to a component of a manufactured article. The method involves forming a suitable flowable material, controlling the manner in which the flowable material is applied, and treating the component before applying the flowable material. In addition, the method may be particularly suitable for applying the flowable material to surfaces and components in automotive, aerospace and marine vehicles.
[0010] EP3281970A1 relates to a pumpable heat-foamable filler composition and in particular to a pumpable heat-foamable filler composition which, when loaded into a closed portion of a body member such as a pillar of a vehicle and then foamed by the heat of a baking process, is suitable for forming an insulating material for blocking noise during operation of the vehicle.
[0011] US9987785 relates to a method and apparatus for applying an activatable molten flowable material to a substrate made of a synthetic material. The method involves forming an appropriate flowable material, controlling the manner in which the flowable material is applied, treating the substrate before applying the flowable material, and selecting an optimal combination of materials for the substrate and the flowable material. The method may be particularly suitable for applying a flowable material to a surface to produce components in automotive, aerospace (including trucks, buses and tractors) and marine vehicles.
[0012] US20060127584 relates to a method and apparatus for applying a molten flowable material to a component of a manufactured article. The method and apparatus involve forming a suitable flowable material, controlling the application mode of the flowable material, and processing the component before applying the flowable material.
[0013] WO2004 / 076507A2 relates to a reactive hot melt composition in the form of free-flowing pellets. The composition comprises 37-60% of a crosslinkable resin based on the total weight of the composition, the crosslinkable resin comprising at least one copolymer of ethylene and an ethylenically unsaturated monomer and wherein the crosslinkable resin comprises an ethylene-acrylic acid copolymer or an ethylene-methacrylic acid copolymer; 10-30% of an adhesion promoter based on the total weight of the composition, the adhesion promoter being a plasticizer and / or a tackifier for providing adhesion to the composition at a temperature of 50-100°C; 0.5-3% of a free radical crosslinking initiator having a 1-hour half-life temperature of 110-170°C based on the total weight of the composition; 10-40% of a filler based on the total weight of the composition and 0.1-4% of a foaming agent based on the total weight of the composition.
[0014] WO2008045270A1 and WO2009058295A2 relate to heat-curing epoxy-based compositions which are said to be pumpable and not easily washed off the substrate surface before curing.
[0015] WO2010023324A1 relates to a reinforcing agent comprising a carrier that is generally conformable to one or more inner walls of a cavity, and an adhesive in one or more beads arranged between the carrier and the one or more inner walls of the cavity, so that when the one or more adhesive beads are cured, the carrier is bonded to the one or more inner walls defining the cavity.
[0016] WO2012041513A1 relates to a foamable adhesive system which can achieve the necessary adhesion to oily surfaces and which is non-tacky once applied to the surface and which has a sufficiently high melt viscosity to maintain its shape and adhesion to the substrate during the baking stage, and which further has a sufficiently high melt viscosity to maintain the bubbles formed by the decomposition of the blowing agent and also maintain its shape and structure once formed by using a polymer system comprising a thixotropic filler and a dual-chamber (component) cross-linking system.
[0017] WO2012104071A2 relates to extruding thermohardenable materials by cooling the material in the initial zone of the extruder and reducing the residence time by using a specified length to diameter ratio and screw speed, particularly useful for intermittent applications during robotically controlled batch production.
[0018] WO2014108857A1 relates to an extrusion process and apparatus for precisely depositing, typically small amounts of, an extrudate to bond to a substrate, comprising an extruder placed close to the substrate and a hot gas jet directed toward the extrudate between the extruder and the substrate to maintain adhesion between the extrudate and the substrate.
[0019] WO2014124924A1 relates to a process for manufacturing a reinforced structural member, in particular a process for forming a part of an automobile or other vehicle or an aircraft or a ship, the reinforced structural member comprising an original structural member and a reinforcement carrier and an adhesive bead and / or a plurality of adhesive blocks arranged between an outer surface of the reinforcement carrier and a contact surface of the original structural member, for structurally bonding the reinforcement carrier to the original structural member.
[0020] US20180273804 relates to applying a heat-activatable adhesive to a substrate, the adhesive being solid at ambient temperature and meltable at a temperature below its heat activation temperature, wherein the adhesive formulation is fed to a hot melt coater, where it is heated to above its melting point and below its activation temperature, and the melt viscosity of the molten adhesive is controlled so that it can be sprayed from the hot melt coater onto a substrate to provide a coherent bead that is bonded to the substrate and is dry to the touch when cooled, and when activated, the adhesive is capable of expanding in volume by greater than about 250%.
[0021] WO2019 / 079026A1 relates to an epoxy-based collision-resistant adhesive composition, comprising: (I) a liquid resin system, comprising: (a) at least one epoxy resin; and (b) at least one toughening agent; wherein the viscosity of the above-mentioned liquid resin system is less than about 800 Pa·s at a temperature of 15°C; and wherein the viscosity of the above-mentioned liquid resin system is greater than about 5 Pa·s at a temperature of 60°C; (II) a solid material, comprising: (c) at least one hydrophobic fumed silica, wherein the fumed silica is present in the adhesive composition at a concentration greater than 5 weight %; and (III) a curing material, comprising: (d) at least one latent heat-activated curing agent; wherein the rheology of the epoxy-based collision-resistant adhesive composition makes the adhesive composition pumpable at a temperature above 15°C; and wherein the epoxy-based collision-resistant adhesive composition exhibits increased resistance to wash-off.
[0022] WO2020212211A1 relates to a thermosetting composition comprising a peroxidically crosslinkable polymer and at least one liquid polymer.
[0023] WO2022 / 162058A1 relates to the field of structural reinforcement, sealing, damping or blocking of elements (preferably hollow structures or cavities) by means of a thermally expandable composition, which comprises (i) a polymer component; (ii) azodicarbonamide; and (iii) a metal oxide powder capable of catalyzing the thermal decomposition of azodicarbonamide at elevated temperatures, wherein at least about 90 wt.-% of the particles in the metal oxide powder have a particle size of up to about 200 μm determined by sieve analysis; wherein the weight ratio of azodicarbonamide to metal oxide powder is at least about 5.0. Summary of the invention
[0024] The properties of prior art curable and pumpable adhesives are unsatisfactory in various aspects and there is a need for improved curable and pumpable adhesives. Known curable and pumpable adhesives do not provide acceptable wash-off resistance and are not pumpable at low temperatures. Therefore, there is a need for a curable and pumpable adhesive having improved wash-off resistance while maintaining the rheological requirements for pumpability at low temperatures.
[0025] It is an object of the present invention to provide a curable polymer composition for use as a sealant, adhesive, reinforcing agent, damping material and / or sound absorbing material having advantages over the prior art.
[0026] The polymer composition should be pumpable, for example, optionally extrudable and wash-off resistant under elevated temperature (extrusion temperature). The polymer composition should be processable at relatively low temperatures, thereby reducing the total energy consumption of processing. For some purposes, the curable polymer composition should be expandable. The curable polymer composition should be applied to the oily surface of a substrate such as a metal plate at moderate temperatures while achieving wash-off resistance. Even when the composition is applied to a substrate surface without a subtending substrate, when the assembly to which the composition is applied is sprayed and bathed, the applied composition is fully exposed to the liquid and should also achieve wash-off resistance.
[0027] This object has been achieved by the subject matter of the patent claims.
[0028] It has surprisingly been found that by combining suitable polymers (resin blends) having appropriate viscosities and melting temperatures (preferably a combination of a first ethylene copolymer, a second ethylene copolymer and an ethylene terpolymer); and by using an appropriate amount of a rheology modifier (preferably one or more layered silicates); the resulting curable polymer composition can be extruded onto a moderately heated (<55°C, substrate temperature) oily substrate, such as a metal plate, while maintaining the wash-off resistance of the composition even when tested under harsh conditions, i.e., when the wash-off resistance test is performed without using an opposing substrate.
[0029] Furthermore, it has been found that the curable and preferably pumpable polymer composition according to the present invention can be used in automated processes, for example can be applied robotically and does not require special tools.
[0030] Furthermore, it has surprisingly been found that the curable and preferably pumpable polymer composition according to the present invention does not require a pre-curing step in order to provide satisfactory wash-off resistance. This improves energy efficiency and has further economic advantages.
[0031] Still further, it has surprisingly been found that the curable polymer composition can be used to replace parts conventionally used for corresponding purposes in automobile construction, such as fenders, preferably with a gap of 70 mm or less, preferably 50 mm or less, and more preferably 20 mm or less between the two substrates to be bonded to each other. The use of the curable and preferably pumpable polymer composition according to the invention in place of conventional fenders is cost-effective, adaptable to various designs of substrates to be bonded to each other, and does not require any additional equipment or tools.
[0032] The curable polymer composition according to the present invention combines the chemistry of optimization with the ability of fully automatic application process. The composition can be extruded and applied directly to the substrate by robot application (robotic application). The composition provides good wash-off resistance and is preferably formulated to be dry to the touch immediately after being extruded onto the substrate, which causes improved operability and can stack or nest multiple parts, thereby minimizing packaging costs. The curable polymer composition according to the present invention is preferably dry to the touch and preferably provides multifunctional design capabilities, excellent green state adhesion and good wash-off resistance. It provides high-level repeatability, improved acoustics and sealing performance, improved operability and minimized packaging costs for applications of different complexity. The composition provides excellent uncured state adhesion to a wide range of substrates and is bonded to most substrates to improve acoustics and sealing performance simultaneously.
[0033] When needed, curable polymer composition according to the present invention can provide high volume expansion in a wide temperature range. It is ideal for long and narrow gaps and cavities and preferably allows the use of conventional pumping equipment for low temperature applications. It eliminates processing costs, can be applied automatically, and provides flexibility after the main design is changed. It can be used as a pumpable baffle suitable for automotive body workshops and is ideal for automated applications in areas where narrow cavities or gap filling are required. Once solidified, it provides excellent adhesion to oily and electrophoretic coated body plates (including all major substrates used in the automotive industry-cold rolling, galvanizing (hot dipping and electroplating) and alloyed hot-dip galvanized steel, and automotive grade aluminum). Curable polymer composition according to the present invention also maintains its adhesion under a series of aging and weathering test conditions. DETAILED DESCRIPTION
[0034] A first aspect of the present invention relates to a curable and preferably pumpable polymer composition for use as a sealant, adhesive, reinforcing agent, damping material and / or sound absorbing material,
[0035] (a) wherein the composition can be deposited onto a surface of an article, preferably a vehicle component, by extrusion at ambient temperature (about 23° C.) or elevated temperature (e.g. about 120° C.) without premature curing (extrusion temperature); wherein after deposition, the composition can be bathed in a liquid coating fluid, preferably an electrocoating bath, without being washed off, preferably without previous pre-curing; and wherein after bathing the composition can be activated to cure by an external stimulus (curing temperature); and / or
[0036] (b) wherein the composition comprises or consists essentially of:
[0037] One or more olefin (e.g. ethylene) polymers, preferably
[0038] (i) a first ethylene copolymer,
[0039] (ii) a second ethylene copolymer, and
[0040] (iii) ethylene terpolymers;
[0041] (iv) a tackifier;
[0042] (v) a curing agent;
[0043] (vi) optionally, a blowing agent;
[0044] (vii) a rheology modifier; preferably one or more layered silicates;
[0045] (viii) optionally, a blowing agent promoter;
[0046] (ix) optionally, a polymerization initiator;
[0047] (x) optionally, a filler (e.g., calcium carbonate, metal oxides, graphite (e.g., graphite flakes), clay, a silicon-containing compound other than layered silicates, or aramid pulp, etc.); and
[0048] (xi) Optionally, a colorant.
[0049] The curable and preferably pumpable polymer composition may have property (a) but not property (b), or property (b) but not property (a), or both properties (a) and (b).
[0050] For the purpose of this specification, "pumpable" means that the composition can be pumped at room temperature (23°C) by means of conventional equipment for applying the adhesive composition to the surface of the substrate. The pumping pressure is usually no more than 50 bar, more preferably no more than 20 bar. For the purpose of this specification, "pumpable" includes "extrudable", and "extrudable" means that the composition can be extruded by a conventional extruder at room temperature (23°C). It is also feasible that the composition according to the present teaching can be pumped or extruded at a temperature above room temperature (e.g., above 23°C, preferably above 75°C, or even above 150°C) but below any activation temperature of any component.
[0051] The curable and preferably pumpable polymer composition according to the present invention preferably comprises one or more olefin polymers, and preferably ethylene polymers, ie homopolymers, copolymers or terpolymers derived from ethylene as monomer and comonomer, respectively.
[0052] The curable and preferably pumpable polymer composition according to the invention preferably comprises a first ethylene copolymer, which preferably comprises or consists essentially of one or more ethylene / butyl acrylate copolymers. When the first ethylene copolymer comprises more than one polymer, for example two different ethylene / butyl acrylate copolymers, all amounts refer to the total content of all polymers comprised by the first ethylene copolymer, unless expressly stated otherwise.
[0053] Preferably, the first ethylene copolymer does not comprise any copolymer having a melt index according to ISO 1133 (190°C / 2.16 kg) higher than 450 g / 10 min, preferably higher than 350 g / 10 min.
[0054] Preferably, at least 40 wt.-%, preferably at least 45 wt.-%, of the first ethylene copolymer, relative to the total content of the first ethylene copolymer, has a melt index according to ISO 1133 (190° C. / 2.16 kg) below 50 g / 10 min. Thus, when the first ethylene copolymer comprises a mixture of two or more different polymers, a quantitative portion thereof is characterized by said property.
[0055] Suitable first ethylene copolymers, such as ethylene / butyl acrylate copolymers, are commercially available, for example as 35BA320 and / or 35BA40 is commercially available.
[0056] Preferably, the content of the first ethylene copolymer is in the range of 45±40 wt.-%, preferably 45±35 wt.-%, more preferably 45±30 wt.-%, still more preferably 45±25 wt.-%, still more preferably 45±20 wt.-%, even more preferably 45±15 wt.-%, most preferably 45±10 wt.-% and in particular 45±5.0 wt.-%, in each case relative to the total weight of the composition.
[0057] Preferably, the first ethylene copolymer comprises or consists essentially of a mixture of:
[0058] - ethylene / butyl acrylate copolymer A, whose melt index according to ISO 1133 (190° C. / 2.16 kg) is in the range of 300±275 g / 10 min, preferably 300±250 g / 10 min, more preferably 300±225 g / 10 min, still more preferably 300±200 g / 10 min, still more preferably 300±175 g / 10 min, even more preferably 300±150 g / 10 min, most preferably 300±100 g / 10 min, and in particular 300±50 g / 10 min; and
[0059] - ethylene / butyl acrylate copolymer B, whose melt index according to ISO 1133 (190°C / 2.16 kg) is in the range of 40±37.5 g / 10 min, preferably 40±35 g / 10 min, more preferably 40±30 g / 10 min, still more preferably 40±25 g / 10 min, still more preferably 40±20 g / 10 min, even more preferably 40±15 g / 10 min, most preferably 40±10 g / 10 min and in particular 40±5.0 g / 10 min.
[0060] Preferably, the first ethylene copolymer comprises or consists essentially of a mixture of:
[0061] - ethylene / butyl acrylate copolymer A, whose content is in the range of 22.5±20.0 wt.-%, preferably 22.5±17.5 wt.-%, more preferably 22.5±15.0 wt.-%, still more preferably 22.5±12.5 wt.-%, still more preferably 22.5±10.0 wt.-%, even more preferably 22.5±7.5 wt.-%, most preferably 22.5±5.0 wt.-% and in particular 22.5±2.5 wt.-%, in each case relative to the total weight of the composition; and
[0062] - ethylene / butyl acrylate copolymer B, whose content is in the range of 22.5±20.0 wt.-%, preferably 22.5±17.5 wt.-%, more preferably 22.5±15.0 wt.-%, still more preferably 22.5±12.5 wt.-%, still more preferably 22.5±10.0 wt.-%, even more preferably 22.5±7.5 wt.-%, most preferably 22.5±5.0 wt.-% and in particular 22.5±2.5 wt.-%, in each case relative to the total weight of the composition.
[0063] The curable and preferably pumpable polymer composition according to the invention preferably comprises a second ethylene copolymer, which preferably comprises or consists essentially of one or more ethylene / vinyl acetate copolymers. When the second ethylene copolymer comprises more than one polymer, for example comprises two different ethylene / vinyl acetate copolymers, all amounts refer to the total content of all polymers comprised by the second ethylene copolymer, unless expressly stated otherwise.
[0064] Preferably, the second ethylene copolymer does not comprise any copolymer having a melt index according to ISO 1133 (190°C / 2.16 kg) higher than 1000 g / min, preferably higher than 900 g / 10 min.
[0065] Preferably, at least 40 wt.-%, preferably at least 45 wt.-%, of the second ethylene copolymer, relative to the total content of the second ethylene copolymer, has a melt index according to ISO 1133 (190° C. / 2.16 kg) below 50 g / 10 min. Thus, when the second ethylene copolymer comprises a mixture of two or more different polymers, a quantitative portion thereof is characterized by said property.
[0066] Suitable second ethylene copolymers, such as ethylene / vinyl acetate copolymers, are commercially available, for example as 28-800, 2805 or UL 7760.
[0067] Preferably, the content of the second ethylene copolymer is in the range of 7.5±7.0 wt.-%, preferably 7.5±6.5 wt.-%, more preferably 7.5±6.0 wt.-%, yet more preferably 7.5±5.5 wt.-%, still more preferably 7.5±5.0 wt.-%, even more preferably 7.5±4.5 wt.-%, most preferably 7.5±4.0 wt.-% and in particular 7.5±3.5 wt.-%, in each case relative to the total weight of the composition.
[0068] Preferably, the second ethylene copolymer comprises or consists essentially of a mixture of:
[0069] - ethylene / vinyl acetate copolymer C having a melt index according to ISO 1133 (190° C. / 2.16 kg) in the range of 800±750 g / 10 min, preferably 800±700 g / 10 min, more preferably 800±600 g / 10 min, still more preferably 800±500 g / 10 min, still more preferably 800±400 g / 10 min, even more preferably 800±300 g / 10 min, most preferably 800±200 g / 10 min and in particular 800±100 g / 10 min; and
[0070] - ethylene / vinyl acetate copolymer D, whose melt index according to ISO 1133 (190°C / 2.16 kg) is in the range of 6.5±5.0 g / 10 min, preferably 6.5±4.5 g / 10 min, more preferably 6.5±30 g / 4.0 min, still more preferably 6.5±3.5 g / 10 min, still more preferably 6.5±3.0 g / 10 min, even more preferably 6.5±2.5 g / 10 min, most preferably 6.5±2.0 g / 10 min and in particular 6.5±1.5 g / 10 min.
[0071] Preferably, the second ethylene copolymer comprises or consists essentially of a mixture of:
[0072] - ethylene / vinyl acetate copolymer C, whose content is in the range of 3.75±3.50 wt.-%, preferably 3.75±3.25 wt.-%, more preferably 3.75±3.00 wt.-%, still more preferably 3.75±2.50 wt.-%, still more preferably 3.75±2.00 wt.-%, even more preferably 3.75±1.50 wt.-%, most preferably 3.75±1.00 wt.-% and in particular 3.75±0.50 wt.-%, in each case relative to the total weight of the composition; and
[0073] - ethylene / vinyl acetate copolymer D, in each case in the range of 3.75±3.50 wt.-%, preferably 3.75±3.25 wt.-%, more preferably 3.75±3.00 wt.-%, still more preferably 3.75±2.50 wt.-%, still more preferably 3.75±2.00 wt.-%, even more preferably 3.75±1.50 wt.-%, most preferably 3.75±1.00 wt.-% and in particular 3.75±0.50 wt.-%, relative to the total weight of the composition.
[0074] The curable and preferably pumpable polymer composition according to the invention preferably comprises an ethylene terpolymer, which ethylene terpolymer preferably comprises or consists essentially of: one or more reactive ethylene terpolymers. When the ethylene terpolymer comprises more than one polymer, for example comprises two different ethylene terpolymers, all amounts refer to the total content of all polymers comprised by the ethylene terpolymer, unless expressly stated otherwise.
[0075] Preferably, the ethylene terpolymer comprises or consists essentially of one or more reactive elastomeric ethylene terpolymers.
[0076] Preferably, the ethylene terpolymer comprises or consists essentially of one or more butyl acrylate / glycidyl methacrylate / ethylene terpolymers.
[0077] Preferably, at least 40 wt.-%, preferably at least 45 wt.-%, of the ethylene terpolymer, relative to the total content of the ethylene terpolymer, has a melt index according to ISO 1133 (190° C. / 2.16 kg) below 50 g / 10 min. Thus, when the ethylene terpolymer comprises a mixture of two or more different polymers, a quantitative portion thereof is characterized by said property.
[0078] Preferably, the ethylene terpolymer does not comprise any terpolymer having a melt index according to ISO 1133 (190°C / 2.16 kg) higher than 50 g / 10 min, preferably higher than 10 g / 10 min.
[0079] Preferably, the melt index according to ISO 1133 (190°C / 2.16 kg) of the ethylene terpolymer is in the range of 8.0±5.0 g / 10 min, preferably 8.0±4.5 g / 10 min, more preferably 8.0±30 g / 4.0 min, still more preferably 8.0±3.5 g / 10 min, still more preferably 8.0±3.0 g / 10 min, even more preferably 8.0±2.5 g / 10 min, most preferably 8.0±2.0 g / 10 min and in particular 8.0±1.5 g / 10 min.
[0080] Suitable ethylene terpolymers, such as n-butyl acrylate / glycidyl methacrylate / ethylene terpolymers, are commercially available, for example as 4170 is commercially available.
[0081] Preferably, the content of ethylene terpolymer is in the range of 4.5±4.0 wt.-%, preferably 4.5±3.5 wt.-%, more preferably 4.5±3.0 wt.-%, still more preferably 4.5±2.5 wt.-%, still more preferably 4.5±2.0 wt.-%, even more preferably 4.5±1.5 wt.-%, most preferably 4.5±1.0 wt.-% and in particular 4.5±0.5 wt.-%, in each case relative to the total weight of the composition.
[0082] The curable and preferably pumpable polymer composition according to the invention preferably comprises a tackifier. When the tackifier comprises more than one tackifier, for example two different tackifiers, all amounts refer to the total content of all tackifiers comprised by the tackifier unless expressly stated otherwise.
[0083] Preferably, the tackifier comprises or consists essentially of one or more hydrocarbon tackifier resins.
[0084] Preferably, the tackifier comprises or consists essentially of one or more polymerization products from unsaturated aromatic C9- / C10-hydrocarbons.
[0085] Suitable tackifiers, for example hydrocarbon resins; polymerization products from unsaturated aromatic C9- / C10-hydrocarbons, are commercially available, for example as TD100 is commercially available.
[0086] Preferably, neither the tackifier nor the composition comprises a hydroxylated polyester tackifier resin; preferably, neither the tackifier nor the composition comprises any polyester tackifier resin.
[0087] Preferably, the content of tackifier, preferably one or more polymerization products from unsaturated aromatic C9- / C10-hydrocarbons, is greater than 8.0 wt.-%, preferably at least 9.0 wt.-%, more preferably at least 10 wt.-%, even more preferably at least 11 wt.-%, still more preferably at least 12 wt.-%, even more preferably at least 13 wt.-%, most preferably greater than 14 wt.-%, in each case relative to the total weight of the composition.
[0088] Preferably, the content of tackifier, preferably one or more polymerization products from unsaturated aromatic C9- / C10-hydrocarbons, is less than 16 wt.-%, relative to the total weight of the composition.
[0089] The curable and preferably pumpable polymer composition according to the invention preferably comprises a curing agent. When the curing agent comprises more than one curing agent, for example two different curing agents, all amounts refer to the total content of all curing agents comprised by the curing agent unless expressly stated otherwise.
[0090] The curing agent can react with itself and / or with other components of the composition according to the present invention to achieve crosslinking and curing. Preferably, the curing agent can react with one or more ethylene polymers, for example with the first ethylene copolymer, with the second ethylene copolymer, with an ethylene terpolymer, or with any combination thereof.
[0091] The curing reaction is preferably initiated by a free-radical polymerization initiator, preferably a peroxide, which is activatable at elevated temperature (curing temperature).
[0092] Preferably, the curing agent comprises or consists essentially of dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, pentaerythritol tetraacrylate, 1,4-butanediol diacrylate, trimethylolpropane triacrylate, tripropylene glycol diacrylate, diethylene glycol diacrylate, or a mixture thereof; dipentaerythritol pentaacrylate is particularly preferred.
[0093] Suitable curing agents, such as dipentaerythritol pentaacrylate, are commercially available, for example as SR399.
[0094] Preferably, the content of curing agent, preferably dipentaerythritol pentaacrylate, is at most 1.45 wt.-%, preferably at most 1.40 wt.-%, even more preferably at most 1.35 wt.-%, still more preferably at most 1.30 wt.-%, even more preferably at most 1.25 wt.-%, most preferably at most 1.20 wt.-%, in each case relative to the total weight of the composition.
[0095] In a preferred embodiment, the composition according to the invention is cured at elevated temperature (curing temperature), preferably at a temperature of at least 110°C, more preferably at least 120°C, even more preferably at least 130°C, still more preferably at least 140°C, even more preferably at least 150°C, most preferably at least 160°C, and in particular at least 170°C.
[0096] In a preferred embodiment, the composition according to the invention is cured at elevated temperature (curing temperature), preferably at a temperature of at most 200°C, more preferably at most 195°C, still more preferably at most 190°C, still more preferably at most 185°C, even more preferably at most 180°C, most preferably at most 175°C, and in particular at most 170°C.
[0097] The curable and preferably pumpable polymer composition according to the invention is preferably expandable (i.e. its volume can expand after activation). To this end, the curable and preferably pumpable polymer composition according to the invention preferably comprises a blowing agent. When the blowing agent comprises more than one blowing agent, for example comprises two different blowing agents, all amounts refer to the total content of all blowing agents comprised by the blowing agent, unless expressly stated otherwise.
[0098] Preferably, the blowing agent comprises or consists essentially of: one or more chemical blowing agents. Chemical blowing agents may be exothermic or endothermic. However, the composition may include one or more physical blowing agents (e.g., it may include thermoplastic microspheres encapsulating a gas, whereby upon heating, the gas expands and the shell softens thereby increasing its volume; commercial examples of which include those sold under the names those that are sold).
[0099] Preferably, the blowing agent comprises or consists essentially of azodicarbonamide, dinitrosopentamethylenetetramine, dinitroso-pentamethylenetetramine, 4,4'oxy-bis-(benzenesulfonylhydrazine), trihydrazinotriazine and N,N'-dimethyl-N,N'-dinitroso-terephthalamide; azodicarbonamide is particularly preferred. Other blowing agents may include metal carbonates (e.g., sodium bicarbonate) alone or in combination with other blowing agents or reagents (e.g., acids such as citric acid or nitric acid, etc.) for inducing a reaction that releases gas.
[0100] Preferably, the content of blowing agent, preferably azodicarbonamide, is less than 3.5 wt.-%, preferably at most 3.3 wt.-%, even more preferably at most 3.1 wt.-%, still more preferably at most 2.9 wt.-%, even more preferably at most 2.8 wt.-%, most preferably at most 2.7 wt.-%, in each case relative to the total weight of the composition.
[0101] Preferably, the content of blowing agent, preferably azodicarbonamide, is greater than 2.60 wt.-%, relative to the total weight of the composition.
[0102] When the curable and preferably pumpable polymer composition according to the present invention is expandable, it may preferably comprise a blowing agent promoter. When the blowing agent promoter comprises more than one blowing agent promoter, for example comprises two different blowing agent promoters, unless expressly stated otherwise, all amounts refer to the total content of all blowing agent promoters comprised by the blowing agent promoter.
[0103] Preferably, the blowing agent booster comprises or consists essentially of zinc oxide.
[0104] Preferably, the content of blowing agent promoter, preferably zinc oxide, is less than 3.5 wt.-%, preferably at most 3.3 wt.-%, even more preferably at most 3.1 wt.-%, still more preferably at most 2.9 wt.-%, even more preferably at most 2.5 wt.-%, most preferably at most 2.2 wt.-%, in each case relative to the total weight of the composition.
[0105] In a preferred embodiment, the composition according to the invention can expand to a volume of at least 150 vol.-%, preferably at least 200 vol.-%, more preferably at least 250 vol.-%, still more preferably at least 300 vol.-% of its original volume. The degree of volume expansion can be tailored by the amount of blowing agent included in the composition. A suitable amount can be determined by routine experimentation.
[0106] In a preferred embodiment, the composition according to the invention expands at elevated temperature (activation temperature), preferably at a temperature of at least 110°C, more preferably at least 120°C, even more preferably at least 130°C, still more preferably at least 140°C, even more preferably at least 150°C, most preferably at least 160°C, and in particular at least 170°C.
[0107] In a preferred embodiment, the composition according to the invention expands at elevated temperature (activation temperature), preferably at a temperature of at most 200°C, more preferably at most 195°C, still more preferably at most 190°C, still more preferably at most 185°C, even more preferably at most 180°C, most preferably at most 175°C, and in particular at most 170°C.
[0108] The curable and preferably pumpable polymer composition according to the present invention preferably comprises a rheology modifier. When the rheology modifier comprises more than one rheology modifier, for example two different rheology modifiers, unless expressly stated otherwise, all amounts refer to the total content of all rheology modifiers comprised by the rheology modifier.
[0109] Preferably, the rheology modifier comprises or consists essentially of one or more thixotropic rheology modifiers.
[0110] Preferably, the rheology modifier comprises or consists essentially of: one or more silicates; more preferably one or more layered silicates; still more preferably one or more organophilic layered silicates.
[0111] Layered silicates (sheet silicates) are a class of mineral polymeric silicates in which silicon-oxygen tetrahedral groups are linked by sharing three of every four oxygen atoms to form sheets of indefinite extent, with a silicon to oxygen ratio of 2:5, and some of the silicon atoms may be substituted by aluminum (as in mica, chlorite, kaolinite, montmorillonite, hectorite, saponite, fluorohectorite, laponite, magatiide).
[0112] In a preferred embodiment, the layered silicates are independently selected from the group consisting of organophilic layered silicates, hydrophilic synthetic layered silicates, hydrophilic organic layered silicates, natural layered silicates, natural layered silicates intercalated with modifiers, such as alkyl onium ions having reactive sites (see, for example: US2004 0214921A1, US20070191527A1, both incorporated by reference).
[0113] Organophilic phyllosilicates are known to the skilled person and are commercially available. For example, montmorillonite consists of an octahedral sheet of aluminum oxide sandwiched between two opposing tetrahedral sheets of silicon dioxide. 3+ Divalent cations such as Fe 2 + or Mg 2+Isostructural substitution leads to negative charge. Isostructural substitution within the layer generates a negative charge, which is balanced by the alkaline or alkaline earth cations located in the middle layer. In order to make these hydrophilic layered silicates more organophilic, the hydrated cations of the middle layer can be exchanged with cationic surfactants such as alkylammonium ions or imidazolium ions. The layered silicates thus modified are organophilic and therefore more compatible with organic polymers. For details, refer to, for example, S. Benali et al., Chapter 5: PCL / Clay Nano-Biocomposites, in L. Avérous et al., Environmental Sili-cate Nano-Biocomposites, Springer 2012.
[0114] Suitable rheology modifiers, preferably layered silicates, such as organophilic layered silicates, are commercially available, for example as 1958 Commercially available.
[0115] Preferably, the content of rheology modifier, preferably one or more layered silicates, is less than 6.0 wt.-%, preferably at most 5.5 wt.-%, even more preferably at most 5.0 wt.-%, still more preferably at most 4.5 wt.-%, even more preferably at most 4.0 wt.-%, most preferably at most 3.5 wt.-%, in each case relative to the total weight of the composition.
[0116] The curable and preferably pumpable polymer composition according to the present invention preferably comprises a free radical polymerization initiator. When the free radical polymerization initiator comprises more than one free radical polymerization initiator, for example comprises two different free radical polymerization initiators, unless explicitly stated otherwise, all amounts refer to the total content of all free radical polymerization initiators comprised by the free radical polymerization initiator.
[0117] Preferably, the free radical polymerization initiator comprises or consists essentially of one or more organic peroxides.
[0118] Preferably, the free radical polymerization initiator comprises or consists essentially of:
[0119] (i) a first organic peroxide selected from dibenzoyl peroxide; and
[0120] (ii) a second organic peroxide selected from 1,1'-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane peroxide.
[0121] Preferably, the free-radical polymerization initiator comprises dibenzoyl peroxide, wherein the content of dibenzoyl peroxide is less than 0.35 wt.-%, relative to the total weight of the composition.
[0122] Preferably, the free-radical polymerization initiator comprises dibenzoyl peroxide, wherein the content of dibenzoyl peroxide is greater than 0.20 wt.-%, preferably at least 0.25 wt.-%, more preferably at least 0.30 wt.-%, still more preferably at least 0.35 wt.-%, in each case relative to the total weight of the composition.
[0123] The curable and preferably pumpable polymer composition according to the present invention preferably comprises a filler. When the free radical polymerization initiator comprises more than one filler, for example, two different fillers, unless otherwise expressly stated, all amounts refer to the total content of all fillers comprised by the filler. Examples of fillers include one or more of metal oxides, graphite (e.g., graphite flakes), clay, silicon-containing compounds other than layered silicates, or aromatic polyamide pulp, etc.).
[0124] Preferably, the filler comprises or consists essentially of calcium carbonate.
[0125] Preferably, the content of filler, preferably calcium carbonate, is greater than 16.60 wt % relative to the total weight of the composition.
[0126] Preferably, the content of filler, preferably calcium carbonate, is at least 12 wt.-%, preferably at least 13 wt.-%, more preferably at least 14 wt.-%, even more preferably at least 15 wt.-%, still more preferably at least 16 wt.-%, even more preferably at least 16.5 wt.-%, most preferably more than 16.6 wt.-%, in each case relative to the total weight of the composition.
[0127] The curable and preferably pumpable polymer composition according to the invention preferably comprises a colorant. When the colorant comprises more than one colorant, for example two different colorants, all amounts refer to the total content of all colorants comprised by the colorant unless expressly stated otherwise.
[0128] The curable and preferably pumpable polymer composition according to the invention may comprise glass beads.
[0129] In a preferred embodiment, the composition according to the invention comprises no silane-coated amorphous silica; preferably does not comprise any amorphous silica.
[0130] The composition according to the invention may or may not contain epoxy resin. In preferred embodiments of the composition according to the invention, the content of epoxy resin is at most 10 wt.-%, preferably at most 7.5 wt.-%, in each case relative to the total weight of the composition.
[0131] In a preferred embodiment, the composition according to the invention is dry to the touch and / or non-tacky at room temperature (23°C).
[0132] In a further preferred embodiment, the composition according to the invention is viscous at room temperature (23° C.).
[0133] In a preferred embodiment, the composition according to the invention is a one-component composition. However, two-component systems are also contemplated according to the invention.
[0134] In a preferred embodiment, the composition according to the invention has sufficient viscoelasticity and does not shrink when it is processed.
[0135] The composition according to the present invention can be deposited onto the surface of an article, preferably a vehicle component, preferably by extrusion at ambient temperature (extrusion temperature, e.g., about 23° C.) or at elevated temperature (extrusion temperature, e.g., up to about 120° C.) without premature solidification. The article can have ambient temperature or elevated temperature (substrate temperature). The surface of the article can be clean, oily or can carry some other contaminants. It is foreseeable that the composition can interact with oil or other contaminants by reacting with the oil or other contaminants, by dissolving the oil or other contaminants and / or by displacing the oil or other contaminants (e.g., the contaminant or any part or other portion thereof becomes physically and / or chemically assimilated into the composition).
[0136] In a preferred embodiment, the composition according to the invention is not a paste, but a solid (usually at room temperature, i.e. 23° C.). Preferably, the composition according to the invention is granulable, i.e. can be provided in the form of pellets and can be processed in the form of pellets at room temperature, i.e. 23° C.
[0137] Direct processing of pellets has some advantages over direct processing of pasty materials because the material applied by direct processing of pellets becomes solid after application and cooling to ambient temperature, whereas a material that is a paste at ambient temperature does not solidify.
[0138] Before application, the composition according to the invention is then preferably heated to an elevated intermediate temperature at which the composition becomes a paste with a flowable viscosity such that it is pumpable at said elevated intermediate temperature, but neither cures nor expands prematurely. The elevated intermediate temperature is therefore preferably below the curing temperature and below the activation temperature of the blowing agent optionally present. After application, the composition can then be cooled again, or further heated to a higher temperature above the curing temperature and the optional activation temperature of the blowing agent optionally present to cause curing and optionally expansion.
[0139] In other preferred embodiments, the composition according to the invention is a paste (typically at room temperature, ie 23° C.).
[0140] At a temperature of 15°C, the composition according to the invention is preferably a paste having a flowable viscosity such that it is pumpable. Preferably, at a temperature of 15°C, the viscosity of the composition according to the invention is at most 800 Pa·s, more preferably at most 700 Pa·s, still more preferably at most 600 Pa·s, still more preferably at most 500 Pa·s, even more preferably at most 400 Pa·s, most preferably at most 300 Pa·s, and in particular at most 200 Pa·s. In a preferred embodiment, at a temperature of 15°C, the viscosity of the composition according to the invention is in the range of 200 to 800 Pa·s, more preferably in the range of 250 to 400 Pa·s.
[0141] At a temperature of 60° C., the viscosity of the composition according to the present invention is preferably at least 5 Pa·s, more preferably at least 7 Pa·s, still more preferably at least 9 Pa·s, still more preferably at least 11 Pa·s, even more preferably at least 13 Pa·s, most preferably at least 15 Pa·s, and in particular at least 17 Pa·s. In a preferred embodiment, at a temperature of 60° C., the viscosity of the composition according to the present invention is in the range of 5 to 20 Pa·s.
[0142] The property "pumpable" of the composition according to the invention is preferably understood as meaning that at ambient temperature (ie 23°C) the composition has a viscosity suitable for pumping and preferably has a pasty viscosity. -1 The viscosity of the composition is generally in the range of 50 to 500 Pa·s when measured at a shear rate of 1.5 to 2.5 %.
[0143] Preferably, the composition according to the present invention is -1 The viscosity is 280 to 420 Pa·s.
[0144] In a preferred embodiment, the composition according to the invention has a relatively sharp decrease in viscosity when the composition according to the invention is heated to an elevated intermediate temperature.
[0145] Preferably, the composition according to the invention can be heated to a first elevated intermediate temperature T1 and a second elevated intermediate temperature T2 which is 40°C higher than T1 (i.e. T2 = T1 + 40°C); wherein T2 and preferably also T1 are above room temperature (i.e. 23°C); wherein both T1 and T2 are below the curing temperature and below the activation temperature of the blowing agent optionally present; wherein at T1 the composition has a viscosity v1; and wherein at T2 the composition has a viscosity v2; wherein the viscosity ratio v1:v2 is at least 5, preferably at least 10, more preferably at least 15, still more preferably at least 20, still more preferably at least 25, even more preferably at least 30, most preferably at least 35, and in particular at least 40. In a preferred embodiment, T2 is 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C.
[0146] Preferably, the composition according to the invention can be heated to a first elevated intermediate temperature T1 and a second elevated intermediate temperature T2 which is 30°C higher than T1 (i.e. T2 = T1 + 30°C); wherein T2 and preferably also T1 are above room temperature (i.e. 23°C); wherein both T1 and T2 are below the curing temperature and below the activation temperature of the blowing agent optionally present; wherein at T1 the composition has a viscosity v1; and wherein at T2 the composition has a viscosity v2; wherein the viscosity ratio v1:v2 is at least 5, preferably at least 10, more preferably at least 15, still more preferably at least 20, still more preferably at least 25, even more preferably at least 30, most preferably at least 35, and in particular at least 40. In a preferred embodiment, T2 is 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C.
[0147] Preferably, the composition according to the invention can be heated to a first elevated intermediate temperature T1 and a second elevated intermediate temperature T2 which is 20°C higher than T1 (i.e. T2 = T1 + 20°C); wherein T2 and preferably also T1 are above room temperature (i.e. 23°C); wherein both T1 and T2 are below the curing temperature and below the activation temperature of the blowing agent optionally present; wherein at T1, the composition has a viscosity v1; and wherein at T2, the composition has a viscosity v2; wherein the viscosity ratio v1:v2 is at least 5, preferably at least 10, more preferably at least 15, still more preferably at least 20, still more preferably at least 25, even more preferably at least 30, most preferably at least 35, and in particular at least 40. In a preferred embodiment, T2 is 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C.
[0148] Preferably, the composition according to the invention can be heated to a first elevated intermediate temperature T1 and a second elevated intermediate temperature T2 which is 10°C higher than T1 (i.e. T2 = T1 + 10°C); wherein T2 and preferably also T1 are above room temperature (i.e. 23°C); wherein both T1 and T2 are below the curing temperature and below the activation temperature of the blowing agent optionally present; wherein at T1 the composition has a viscosity v1; and wherein at T2 the composition has a viscosity v2; wherein the viscosity ratio v1:v2 is at least 5, preferably at least 10, more preferably at least 15, still more preferably at least 20, still more preferably at least 25, even more preferably at least 30, most preferably at least 35, and in particular at least 40. In a preferred embodiment, T2 is 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C.
[0149] Methods for determining the viscosity of adhesive materials at various temperatures are known to the skilled person.The viscosity is usually measured with the aid of a rotational viscometer, preferably according to ASTM D2196 or ASTM D2556.
[0150] It has been found that by combining a liquid component of known viscosity and a rheology modifier (preferably one or more layered silicates) in appropriate proportions, the rheological requirements of the curable polymer composition according to the present invention for wash-off resistance while maintaining its pumpability at low temperatures can be improved. The curable polymer composition according to the present invention may include a liquid and a solid, wherein the resulting curable polymer composition preferably has a viscosity that satisfies the rheological properties of being pumpable at temperatures as low as 15°C. Generally, one or more other optional liquid components or reactive diluents may be used in an amount effective to reduce the viscosity of the curable polymer composition to a desired level.
[0151] Reactive diluents may also be advantageous for the application of the curable polymer composition according to the invention onto oily surfaces.It has been found that reactive diluents may be useful with regard to the solubilization of oils contaminating, for example, the surfaces of vehicle components.
[0152] The concept of treating oily or otherwise contaminated surfaces can in principle rely on
[0153] - displacement of oil or contamination, for example by treating the surface by mechanical means (for example grinding), by flame, by plasma, by corona, etc., before applying the composition;
[0154] - chemical modification of the oil or contaminants (e.g. by oxidation or reaction with functional groups such as carboxyl and amine groups); or
[0155] - Solubilization of oil or contaminants (eg in a liquid component such as a reactive diluent).
[0156] Chemical modification of the oil or contaminant, such as by oxidation, may be accomplished by heating the oil or contaminant, or by heating the material on which the oil or contaminant is present.
[0157] In a preferred embodiment, the composition according to the invention does not require displacement of oil or contaminants prior to application, nor does it require heating of the oil or contaminants or heating of the material on which the oil or contaminants are present. Compatibility with oily or otherwise contaminated surfaces is preferably achieved by the ingredients contained in the composition according to the invention, preferably by one or more reactive diluents, and / or by one or more optional or additional components, which are preferably liquid in their pure state and can contribute to the solubilization of the oil or contaminants.
[0158] Preferred reactive diluents can be divided into epoxy-containing diluents on the one hand and compounds which derive their reactivity from functional groups other than epoxides (non-epoxy based reactive diluents) on the other hand.
[0159] Preferred epoxy-containing reactive diluents (epoxy-based reactive diluents) can be subdivided into monoepoxides and difunctional / polyfunctional epoxy compounds. In both categories, the presence of epoxy groups allows the diluent to participate in polymerization and crosslinking reactions with the resin and curing agent. The diluent is thus chemically incorporated into the crosslinking network.
[0160] Preferred monofunctional, difunctional or multifunctional epoxy reactive diluents according to the present invention include but are not limited to
[0161] (i) unsaturated, branched or unbranched, cyclic or open chain, aliphatic or aromatic C4-C 30 Oxides of hydrocarbons, such as octane oxide, butadiene dioxide, cyclohexene epoxide compounds, alloocimene dioxide, limonene dioxide, vinylcyclohexane dioxide, styrene oxide, divinylbenzene dioxide, etc.;
[0162] (ii) a monovalent saturated or unsaturated, branched or unbranched, cyclic or open-chain C4-C 30 Glycidyl ethers of alcohols, such as butanol glycidyl ether, hexanol glycidyl ether, 2-ethylhexanol glycidyl ether, allyl glycidyl ether, tetrahydrofurfuryl glycidyl ether, and furfuryl glycidyl ether, trimethoxysilyl glycidyl ether, and the like;
[0163] (iii) dibasic saturated or unsaturated, branched or unbranched, cyclic or open-chain C2-C 30 Glycidyl ethers of alcohols, such as ethylene glycol glycidyl ether, butanediol glycidyl ether, hexanediol glycidyl ether, octanediol glycidyl ether, diethylene glycol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, neopentyl glycol diglycidyl ether, etc.;
[0164] (iv) glycidyl ethers of tri- or polyhydric, saturated or unsaturated, branched or unbranched, cyclic or open-chain alcohols, for example epoxidized castor oil, epoxidized trimethylolpropane, triglycidyl ether of trimethylolpropane, epoxidized pentaerythritol, or polyglycidyl ethers of aliphatic polyols, for example sorbitol, glycerol, trimethylolpropane, diglycidyl ether of cyclohexanedimethanol (e.g. 757) etc.;
[0165] (v) glycidyl ethers of phenolic compounds and glycidyl ethers of aniline compounds, such as phenyl glycidyl ether, monoglycidyl ethers of alkyl- and alkenyl-substituted phenols, cresyl glycidyl ether, diglycidyl ether of resorcinol, p-tert-butylphenyl glycidyl ether, nonylphenol glycidyl ether, 3-n-pentadecenyl-glycidyl ether (from cashew nut shell liquid), epoxidized cashew nut shell liquid (CNSL, such as cardanol, cardanol and / or methyl cardanol, such as NC-514 or Lite 2513HP), N,N-diglycidylaniline, etc.
[0166] (vi) Epoxy amines, such as N,N-diglycidylcyclohexylamine, etc.;
[0167] (vii) epoxidized mono- or dicarboxylic acids, such as glycidyl neodecanoate (e.g. GS-110), glycidyl methacrylate, glycidyl benzoate, diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl hexahydrophthalate, glycidyl esters of tertiary carboxylic acids, diglycidyl dimer fatty acids, etc.
[0168] (viii) Epoxidized di- or tri-hydric, low to high molecular weight polyether polyols, such as polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and the like.
[0169] Preferred non-epoxy reactive diluents include, but are not limited to, triphenyl phosphite, lactone compounds such as butyrolactone, hydroxydioxane, limonene, tetrahydrofuran, furfuryl alcohol, mesityl oxide, and the like.
[0170] The composition according to the invention may contain additional ingredients such as thermoplastic polymers and elastomers and the like.
[0171] In a preferred embodiment, the composition comprises polyvinyl chloride (PVC), such as a polyvinyl chloride homopolymer or copolymer. If the polyvinyl chloride is a copolymer, it preferably comprises a vinyl ester such as vinyl acetate or vinyl propionate as a comonomer of the vinyl chloride. The amount of comonomer is typically in the range of about 1 to about 20 wt.-%, more typically in the range of 2 to about 10 wt.-%, and most preferably about 5 wt.-%, relative to the total weight of the copolymer.
[0172] In a preferred embodiment, the composition according to the invention comprises an acrylic resin powder which is solid at ambient temperature (23° C.). Preferably, the glass transition temperature Tg of the acrylic resin powder is in the range of 50° C. to 120° C. and even more preferably in the range of 70° C. to 90° C. The glass transition temperature is determined by DSC. In addition, it is preferred that the acrylic resin powder is capable of forming a plastisol. The acrylic resin in the acrylic resin powder may be a homopolymer or a copolymer. Preferred acrylic resins are resins based on methyl methacrylate.
[0173] In a preferred embodiment, the composition according to the present invention comprises rubber, in particular synthetic rubber and preferably partially crosslinked synthetic rubber. Exemplary partially crosslinked rubbers include, but are not limited to, diene rubbers, such as acrylonitrile-isoprene copolymer rubber (NIR), acrylonitrile-butadiene copolymer rubber (NBR), styrene-butadiene copolymer rubber (SBR), butadiene rubber (BR) and isoprene rubber (IR). Crosslinking can be the result of adding a crosslinking agent such as divinylbenzene or sulfur. The addition of rubber provides the advantages of improved rheological properties, anti-sagging, wash-off resistance and higher volume expansion of the resulting filler composition. Relative to the gross weight of the composition, the rubber is generally introduced in an amount of 1 to 20 wt.-%, preferably 3 to 15 wt.-% and more preferably 5 to 10 wt.-%.
[0174] In a preferred embodiment, the composition according to the invention comprises a plasticizer. Preferred plasticizers are, for example, phthalates such as di(2-ethylhexyl)phthalate, butyl benzyl phthalate, dinonyl phthalate, diisononyl phthalate (DIDP), diisodecyl phthalate (DIDP), heneicosyl phthalate, tricosyl phthalate (DTDP), diheptyl phthalate and butylphthaloyl butyl glycolate; aliphatic dibasic acid esters such as dioctyl adipate, didecyl adipate and dioctyl sebacate; polyethylene glycol benzoates such as polyoxyethylene glycol dibenzoate and polyoxypropylene glycol dibenzoate; phosphates such as tributyl phosphate and tricresyl phosphate; hydrocarbons such as alkyl-substituted diphenyls, alkyl-substituted terphenyls, partially hydrogenated terphenyls, aromatic processing oils and pile oils. These plasticizers may be used alone or as a mixture of two or more thereof. A suitable amount of the plasticizer is 5 to 40 wt.-%, preferably 8 to 30 wt.-%, and particularly 10 to 20 wt.-%, relative to the total weight of the composition.
[0175] After deposition, the composition according to the invention can preferably be bathed in a liquid coating fluid, preferably an electrocoating bath, without being washed off.
[0176] For the purposes of this specification, the terms "wash off" and "wash out" are used synonymously.
[0177] Preferably, the composition according to the invention passes a wash-off test involving the following steps:
[0178] (a) Apply beads of the composition to an oil loading of 1.5 g / m 2 (Preferred PL3802-39S, 1.5g / m 2 =0.12 g) on the surface of a stainless steel specimen (preferably a hot-dip galvanized steel plate (DX54D+Z100, 200×40 mm)), wherein the steel plate is used as a substrate (base plate) without a counter substrate (top plate);
[0179] (b) without pre-curing, the sample thus prepared was placed in an immersion fixture and dropped unhindered from a height of 20 cm into a tank filled with room temperature (23° C.) pure water;
[0180] (c) installing the sample into a stirrer in a second tank filled with pure water preheated to 55° C.;
[0181] (d) stirring the sample at 60 rpm (0.82 m / s) for 3 min;
[0182] (e) The sample is removed and visually inspected, wherein the adhesive composition passes the wash-off resistance test when no significant change in the adhesive composition is detected.
[0183] Preferably, the composition according to the invention passes the wash-off test according to BMW standard AA-0044 from January 2018. The test is similar to the above test but the test conditions are more severe: 60°C instead of 55°C, and 140rpm (1.47m / s) instead of 60rpm (0.82m / s). Therefore, the wash-off test preferably involves the following steps:
[0184] (a) Apply beads of the composition to an oil loading of 1.5 g / m 2 (Preferred PL3802-39S, 1.5g / m 2 =0.12 g) on the surface of a stainless steel specimen (preferably a hot-dip galvanized steel plate (DX54D+Z100, 200×40 mm)), wherein the steel plate is used as a substrate (base plate) without a counter substrate (top plate);
[0185] (b) without pre-curing, the sample thus prepared was placed in an immersion fixture and dropped unhindered from a height of 20 cm into a tank filled with room temperature (23° C.) pure water;
[0186] (c) installing the sample into a stirrer in a second tank filled with pure water preheated to 60° C.;
[0187] (d) stirring the sample at 140 rpm (1.47 m / s) for 3 min;
[0188] (e) The sample is removed and visually inspected, wherein the adhesive composition passes the wash-off resistance test when no significant change in the adhesive composition is detected.
[0189] Due to the wash-off resistance, the composition is compatible with electrocoating processes commonly used in the manufacture of various vehicles.
[0190] In a further preferred embodiment, the composition according to the invention passes the wash-off resistance test for adhesives and sealants according to General Motors GMW 16700, preferably in the 2nd edition of February 2017.
[0191] In a further preferred embodiment, the composition according to the present invention passes the ADS-5 wash-off resistance test according to SAE International's test method for automotive sealants, adhesives and sound insulation materials (standardized in January 2021) J243_202101.
[0192] In a preferred embodiment, the composition according to the invention is heat-activated for curing and optionally expansion. After the immersion bath, the composition according to the invention can be activated for curing preferably by external stimulation, preferably at an elevated temperature above the curing temperature and optionally above the activation temperature of the blowing agent optionally present.
[0193] Preferably, the compositions according to the present invention provide excellent weather resistance and do not show bond-line read-through. That is, after application and curing, visible deformation of substrates such as metal sheets at the cured adhesive bond line is avoided. For example, the composition for use in motor vehicles can withstand repeated (e.g., at least 100 cycles over a period of at least 100 hours) thermal cycling (e.g., between temperatures of -40°C and 125°C) over time without causing any such deformation.
[0194] Another aspect of the present invention relates to a motor vehicle assembly comprising:
[0195] -Transportation components and
[0196] - Extruded beads of a curable and preferably pumpable polymer composition according to the invention as described above on the surface of a vehicle component.
[0197] For the purpose of this specification, the term "bead" includes any geometric shape, such as granules, globules, spheres, squares, rectangles, and wires, etc. The cross-section of the bead can have any geometric shape, such as circles, ellipses, rectangles, triangles, diamonds, trapezoids, etc.
[0198] The die used for extrusion can also have any geometric shape, such as circular, oval, rectangular, triangular, diamond, trapezoidal, etc.
[0199] Preferably, the extruded beads withstand one or more of the wash-off tests described above.
[0200] Preferably, the extruded beads exhibit resiliency in response to loads encountered during manufacturing operations.
[0201] The surface of the article to which the composition is applied is preferably a vehicle component. The vehicle is not particularly limited and includes, for example, automobiles with internal combustion engines or electric vehicles, other electric vehicles, and railway vehicles, and the like.
[0202] Preferably, the vehicle component is selected from the group consisting of a vehicle hood, a vehicle roof, a roof bow, a vehicle door, a door beam, a tubular frame member, a vehicle bumper, a front fender flare, a vehicle door sill, a vehicle pillar such as an A-pillar (preferably the lower or upper outer section thereof) or a B-pillar (preferably the lower or upper outer section thereof), a pillar closure, a vehicle suspension component, a vehicle support member, a side impact beam, a reinforcement bar, a vehicle skin, a vehicle hood, a vehicle trunk, a taillight, a fuel filler, a battery housing, a battery support or any combination thereof.
[0203] The compositions according to the invention are also useful as hem flange adhesives.
[0204] The composition according to the invention can be applied to a substrate, essentially requiring the following:
[0205] - 2D applications (e.g. door beams, roof bows, simple linear geometries),
[0206] - Intermediate 3D applications (e.g. small to medium complex 3D geometries, fender flares), or
[0207] - Large 3D applications (eg hood supports, fender flares, door inners).
[0208] In a preferred embodiment, the extruded beads (which may be applied as a single continuous strip or as a plurality of intermittently spaced strips) have the following:
[0209] (i) an extrusion axis along the direction of movement of the die relative to the substrate to which the beads are applied;
[0210] (ii) an average cross-sectional area (measured in a section perpendicular to the extrusion axis) of at least 0.1 cm 2 , preferably at least 1.0 cm 2 , more preferably at least 2.0 cm 2 ; and up to 10cm 2 , preferably at most 8.0 cm 2 , more preferably at most 6.0 cm 2 , and still more preferably at most 4.0 cm 2 ;
[0211] (iii) a cross-sectional profile along the extrusion axis that is circular, elliptical, hemispherical, rectangular, polygonal, has multiple lobes, or any combination thereof; and / or
[0212] (iv) a length of at least 1.0 cm, preferably at least 5.0 cm, more preferably at least 10 cm, and still more preferably at least 20 cm; and at most 1000 cm, preferably at most 750 cm, more preferably at most 500 cm, still more preferably at most 300 cm, and still more preferably at most 100 cm; and / or
[0213] (v) the maximum dimension of the cross-sectional profile (e.g., width or diameter, etc.) is at most 20 cm, preferably at most 10 cm, more preferably at most 5 cm, and even more preferably at most 2 cm or 1 cm; and / or the minimum dimension of the cross-sectional profile is at most 5 cm, preferably at most 3 cm, more preferably at most 1 cm, and even more preferably at most 0.5 cm or 0.1 cm.
[0214] In a preferred embodiment, the beads form a closed loop, and loop closure is preferably achieved by applying one end of the bead to the other end of the bead in an overlapping manner.
[0215] The beads may have any shape such as linear or curved.
[0216] The size of the bead may vary along its length. For example, the height and / or width may increase along its length.
[0217] In preferred embodiments, the beads fill a gap having a maximum length L, a maximum width W, and a maximum depth D, wherein (i) L>W>D or (ii) L>D>W or (iii) L>D=W.
[0218] In a preferred embodiment, the beads fill the gap between two substrates to be bonded to each other, preferably the gap between the surface of the vehicle component and the surface of the opposing substrate. Preferably, the gap between the two substrates, at least in a local area, is 70 mm or less, preferably 50 mm or less, and more preferably 20 mm or less; preferably at most 18 mm, more preferably at most 16 mm, still more preferably at most 14 mm, still more preferably at most 12 mm, even more preferably at most 10 mm, most preferably at most 8 mm, and in particular at most 6 mm.
[0219] In a preferred embodiment, the motor vehicle assembly comprises multiple layers of beads, preferably extruded on top of each other.Preferably, the motor vehicle assembly comprises two layers of beads, three layers of beads, four layers of beads, five layers of beads, six layers of beads or seven layers of beads.
[0220] Another aspect of the invention relates to a method for producing a motor vehicle assembly according to the invention as described above, the method comprising the following steps:
[0221] (a) providing a vehicle component having a surface (e.g., exterior and / or interior); and
[0222] (b) Extruding beads of the curable polymer composition through an extrusion device and directly onto a surface of a vehicle component (optionally extruding the beads into a cavity defined by an interior surface of the component).
[0223] The component may have a wall defining a surface onto which beads of the composition are extruded. The wall may have an average thickness (e.g., less than 1 cm, more preferably less than 0.5 cm). The component may be sheet metal, cast metal, injection molded plastic, extruded plastic, pultruded plastic, consolidated fiber material in a polymer matrix, or any combination thereof. Preferably, the temperature of the surface of the vehicle component is controlled.
[0224] Preferably, the temperature of the surface of the vehicle component (substrate temperature) when the beads contact the surface of the vehicle component throughout the duration of extrusion is at most 65°C, preferably at most 60°C, more preferably at most 55°C, even more preferably at most 50°C, still more preferably at most 45°C, even more preferably at most 40°C, most preferably at most 35°C, and in particular at most 30°C.
[0225] Various temperatures may play an important role and it seems appropriate to distinguish at least the following temperatures:
[0226] (i) the temperature of the composition according to the invention during step (b) (also referred to herein as "extrusion temperature");
[0227] (ii) the temperature of the vehicle component and its respective surface (also referred to herein as "substrate temperature");
[0228] (iii) the temperature of the motor vehicle assembly after step (b) and before step (c) (see below) (also referred to herein as the "no pre-cure temperature");
[0229] (iv) the temperature of the liquid fluid in which the motor vehicle assembly is immersed (also referred to herein as the "liquid temperature");
[0230] (v) the temperature at which the composition as part of a motor vehicle assembly is ultimately cured (also referred to herein as the "cure temperature"); and
[0231] (vi) Optionally, when the composition comprises a heat-activatable blowing agent, the temperature at which volume expansion is induced by activation of the blowing agent (also referred to herein as the "activation temperature").
[0232] Preferably, the surface of the vehicle component provided in step (a) is oily.
[0233] Preferably, step (b) is performed robotically.
[0234] In a preferred embodiment, the extrusion in step (b) is carried out at a temperature of the curable polymer composition (extrusion temperature) which is ambient temperature (eg 23° C.), ie the curable polymer composition is not actively heated for the purpose of extrusion.
[0235] In other preferred embodiments, the extrusion in step (b) is carried out at a temperature of the curable polymer composition (extrusion temperature) which is above ambient temperature (eg 23° C.), ie the curable polymer composition is actively heated for the purpose of extrusion.
[0236] Preferably, the extrusion in step (b) is carried out at a temperature of the curable polymer composition (extrusion temperature) of at most 65°C, preferably at most 60°C, more preferably at most 55°C, still more preferably at most 50°C, still more preferably at most 45°C, even more preferably at most 40°C, most preferably at most 35°C, and in particular at most 30°C.
[0237] In a preferred embodiment, step (b) comprises extruding multiple layers of beads, preferably on top of each other. Preferably, step (b) comprises the following sub-steps:
[0238] (b1) Extruding beads of a curable polymer composition through an extrusion device and directly onto a surface of a vehicle component (optionally extruding the beads into a cavity defined by an interior surface of the component).
[0239] (b2) extruding a second bead of the curable polymer composition through an extrusion device and directly onto a surface of the bead, the bead being directly extruded onto a surface of a vehicle component;
[0240] (b3) optionally, extruding a third bead of the curable polymer composition through an extrusion device and directly onto the surface of the second bead;
[0241] (b4) optionally, extruding a fourth bead of the curable polymer composition through an extrusion device and directly onto the surface of the third bead; and
[0242] (b5) Optionally, extruding fifth beads of the curable polymer composition through an extrusion device and directly onto the surface of the fourth beads.
[0243] Step (b) may include further sub-steps similar to steps (b2) to (b5) for extruding more beads, such as a sixth bead and a seventh bead. Thus, step (b) may include extruding multiple layers of beads on top of each other, such as extruding two layers of beads, three layers of beads, four layers of beads, five layers of beads, six layers of beads or seven layers of beads.
[0244] Preferably, the method comprises the following additional steps:
[0245] (c) immersing the vehicle component having the extruded beads on its surface into a bath of liquid coating fluid, preferably an electrocoating bath.
[0246] Preferably, after extrusion in step (b) until immersion in step (c), the temperature of the motor vehicle assembly is independently maintained at a temperature of at most 65° C., preferably at most 60° C., more preferably at most 55° C., still more preferably at most 50° C., still more preferably at most 45° C., even more preferably at most 40° C., most preferably at most 35° C., and in particular at most 30° C. (without pre-curing temperature). Said temperature of the motor vehicle assembly after extrusion in step (b) until immersion in step (c) may be different from the extrusion temperature and the substrate temperature.
[0247] Preferably, the vehicle component having the extruded beads on its surface is immersed in various baths including one or more of a degreasing bath, a phosphating bath, a rinsing bath, and an electrocoating bath.
[0248] Preferably, the process is without any step of pre-curing (pre-baking) the motor vehicle assembly or the extruded beads of curable polymer composition prior to the immersion in step (c).
[0249] Preferably, the method is free of any step of applying a counter substrate to the motor vehicle assembly or the extruded beads of curable polymer composition prior to the immersion in step (c).
[0250] Preferably, the method comprises the following additional steps:
[0251] (d) heating the motor vehicle assembly or extruded beads of the curable polymer composition to a temperature that is above the curing temperature of the curable polymer composition to cause curing; and optionally above the activation temperature of an optionally present blowing agent to cause volume expansion.
[0252] Preferably, during step (d), the curable polymer composition on the surface of the vehicle component is bonded to the surface of the opposing substrate. Preferably, during step (d), the curable polymer composition on the surface of the vehicle component expands so as to contact with the surface of the opposing substrate. Preferably, before performing step (d), at least in the local area, the gap between the surface of the vehicle component and the surface of the opposing substrate is 70mm or less, preferably 50mm or less, and more preferably 20mm or less; preferably at most 18mm, more preferably at most 16mm, still more preferably at most 14mm, still more preferably at most 12mm, even more preferably at most 10mm, most preferably at most 8mm, and particularly at most 6mm or even 4mm.
[0253] Another aspect of the invention relates to the use of a curable and preferably pumpable polymer composition according to the invention as described above, preferably in a process according to the invention as described above, for producing a motor vehicle assembly according to the invention as described above.
[0254] In a preferred embodiment, the curable and preferably pumpable polymer composition according to the invention is used, for example, for the joint between a reinforcing bar and a skin, a door, a roof, an engine hood or a trunk. The applied uncured polymer composition, even when applied to the surface of a substrate without a counter substrate, is resistant to washing off in subsequent treatment baths and electrocoating treatments.
[0255] The curable and preferably pumpable polymer compositions according to the present invention are used throughout the vehicle and service all body shop categories; anti-collision, structural, hemming and anti-flutter products. When used for anti-collision joints, the compositions according to the present invention help to significantly increase energy absorption during a collision event. Superior impact peel values and reduced body intrusion space provide an effective joining solution for high-performance vehicles. When used for structural joints, the compositions according to the present invention provide several performance and process benefits, including increased body stiffness, excellent oil absorption, wash-out resistance, long-term corrosion resistance, a significant reduction in the number of spot welds and a long shelf life. When used for anti-flutter and spot welding paste sealing applications, the compositions according to the present invention provide excellent adhesion to standard OEM steel and aluminum substrates. The compositions according to the present invention provide vibration-free plate isolation connections while also protecting durable metals from corrosion associated with component aging. The compositions according to the present invention can prevent bond line penetration (BLRT) and will not reduce the strength of the welds. The compositions according to the present invention can also be used as spot welding paste adhesives.
[0256] The curable and preferably pumpable polymer composition according to the invention is used for hem flanges.
[0257] Other teachings that are generally applicable to all embodiments and can be combined with each other include the following.
[0258] The beads may be extruded onto a surface and a carrier or other article may be compressively applied to the beads (e.g., it may be a bead of adhesive that does not contain any blowing agent and will not form a foam) squeezed between two surfaces).
[0259] The component having the beads of the present teachings applied thereto may be a carrier for a structural reinforcement, for a baffle, or a combination thereof, and / or such a component may also carry a second activatable material that differs in composition relative to the beads of the present composition.
[0260] The beads may be applied to opposing exterior surfaces of a carrier to result in joining two different components of the vehicle to the carrier within a motor vehicle. For example, opposing formed sheet metal sections welded together at a joint to define a cavity may have the carrier positioned in the cavity, and (i) the adhesive of the invention joins the carrier to each sheet metal section; (ii) the sheet metal joint is joined with the adhesive; and / or both (i) and (ii).
[0261] The beads can be applied to a carrier having a plurality of cellular cavities defined therein, the length, width and / or depth of the cellular cavities being at least 1 cm, preferably at least 2 cm, and less than 5 cm, and preferably less than 3 cm. The cavity can be open and at least partially surrounded by three, four, five or six walls. The cellular cavity (cell) can be defined by a plurality of substantially flat sidewalls. The sidewalls defining the cellular cavity can be connected to each other to define a polygon (e.g., a rectangle, a hexagon or other). The wall defining any cellular cavity may include one or more through holes. The carrier may include one or more integrally formed fasteners (e.g., clips or other structures that will penetrate the opening in the vehicle assembly and interfere with the carrier being fixed to the assembly).
[0262] The following examples further illustrate the present invention but should not be construed as limiting its scope.
[0263] The following composition according to the invention is made by blending all ingredients with one another:
[0264]
Claims
1. A curable polymer composition for use as a sealant, adhesive, reinforcing agent, damping material and / or sound absorbing material, (a) wherein the composition is capable of being deposited onto the surface of an article by extrusion at ambient or elevated temperature; wherein after deposition the composition is capable of being bathed in a liquid coating fluid without being washed off; and wherein after bathing the composition is capable of being activated to cure by an external stimulus; and / or (b) wherein the composition comprises or consists essentially of: - one or more ethylene polymers; preferably (i) a first ethylene copolymer; (ii) a second ethylene copolymer; and (iii) ethylene terpolymers; - (iv) a tackifier; - (v) a curing agent; -(vi) optionally, a blowing agent; - (vii) a rheology modifier; preferably one or more layered silicates; - (viii) optionally, a blowing agent promoter; -(ix) optionally, a polymerization initiator; - (x) optionally, a filler; and - (xi) optionally, a colorant.
2. The composition of claim 1, wherein the rheology modifier comprises or consists essentially of: One or more silicates; more preferably one or more layered silicates; even more preferably one or more organophilic layered silicates.
3. The composition according to claim 1 or 2, wherein the tackifier comprises or consists essentially of: One or more polymerization products from unsaturated aromatic C9- / C10-hydrocarbons.
4. A composition according to any preceding claim which does not comprise a hydroxylated polyester tackifier resin; preferably it does not comprise any polyester tackifier resin.
5. A composition according to any preceding claim which does not comprise silane-coated amorphous silica; preferably it does not comprise any amorphous silica.
6. Composition according to any of the preceding claims, wherein the content of tackifier, preferably one or more polymerization products from unsaturated aromatic C9- / C10-hydrocarbons, is greater than 8.0 wt.-%, preferably at least 9.0 wt.-%, more preferably at least 10 wt.-%, even more preferably at least 11 wt.-%, still more preferably at least 12 wt.-%, even more preferably at least 13 wt.-%, most preferably greater than 14 wt.-%, in each case relative to the total weight of the composition.
7. Composition according to any of the preceding claims, wherein the content of tackifier, preferably one or more polymerization products from unsaturated aromatic C9- / C10-hydrocarbons, is less than 16 wt.-%, relative to the total weight of the composition.
8. Composition according to any of the preceding claims, wherein the content of curing agent, preferably dipentaerythritol pentaacrylate, is at most 1.45 wt.-%, preferably at most 1.40 wt.-%, even more preferably at most 1.35 wt.-%, still more preferably at most 1.30 wt.-%, even more preferably at most 1.25 wt.-%, most preferably at most 1.20 wt.-%, in each case relative to the total weight of the composition.
9. A composition according to any of the preceding claims, wherein the content of blowing agent, preferably azodicarbonamide, is less than 3.5 wt.-%, preferably at most 3.3 wt.-%, even more preferably at most 3.1 wt.-%, still more preferably at most 2.9 wt.-%, even more preferably at most 2.8 wt.-%, most preferably at most 2.7 wt.-%, in each case relative to the total weight of the composition.
10. A composition according to any of the preceding claims, wherein the content of rheology modifier, preferably one or more layered silicates, is less than 6.0 wt.-%, preferably at most 5.5 wt.-%, even more preferably at most 5.0 wt.-%, still more preferably at most 4.5 wt.-%, even more preferably at most 4.0 wt.-%, most preferably at most 3.5 wt.-%, in each case relative to the total weight of the composition.
11. A composition according to any of the preceding claims, wherein the content of blowing agent promoter, preferably zinc oxide, is less than 3.5 wt.-%, preferably at most 3.3 wt.-%, even more preferably at most 3.1 wt.-%, still more preferably at most 2.9 wt.-%, even more preferably at most 2.5 wt.-%, most preferably at most 2.2 wt.-%, in each case relative to the total weight of the composition.
12. The composition according to any of the preceding claims, wherein the free-radical polymerization initiator comprises dibenzoyl peroxide, wherein the content of dibenzoyl peroxide is greater than 0.20 wt.-%, preferably at least 0.25 wt.-%, more preferably at least 0.30 wt.-%, still more preferably at least 0.35 wt.-%, in each case relative to the total weight of the composition.
13. A composition according to any of the preceding claims, wherein the content of filler, preferably calcium carbonate, is at least 12 wt.-%, preferably at least 13 wt.-%, more preferably at least 14 wt.-%, even more preferably at least 15 wt.-%, still more preferably at least 16 wt.-%, even more preferably at least 16.5 wt.-%, most preferably more than 16.6 wt.-%, in each case relative to the total weight of the composition.
14. Composition according to any of the preceding claims, wherein the content of blowing agent, preferably azodicarbonamide, is greater than 2.60 wt.-%, relative to the total weight of the composition.
15. The composition according to any of the preceding claims, wherein the free-radical polymerization initiator comprises dibenzoyl peroxide, wherein the content of dibenzoyl peroxide is less than 0.35 wt.-%, relative to the total weight of the composition.
16. A composition according to any of the preceding claims, wherein the content of filler, preferably calcium carbonate, is greater than 16.60 wt% relative to the total weight of the composition.
17. A composition according to any preceding claim which is not a paste at 23°C.
18. A composition according to any of claims 1 to 16 which is a paste at 23°C.
19. A composition according to any preceding claim which is a one component composition.
20. A composition according to any preceding claim which is heat activatable for curing and optionally expansion.
21. A composition according to any of the preceding claims, which cures at elevated temperature, preferably at a temperature of: - at least 110°C, more preferably at least 120°C, still more preferably at least 130°C, still more preferably at least 140°C, even more preferably at least 150°C, most preferably at least 160°C, and in particular at least 170°C; and / or - at most 200°C, more preferably at most 195°C, still more preferably at most 190°C, still more preferably at most 185°C, even more preferably at most 180°C, most preferably at most 175°C, and in particular at most 170°C.
22. The composition according to any of the preceding claims, which is expandable, preferably to a volume of at least 150 vol.-%, preferably at least 200 vol.-%, more preferably at least 250 vol.-%, still more preferably at least 300 vol.-% of its original volume.
23. A composition according to any of the preceding claims which expands at elevated temperature, preferably at a temperature of: - at least 110°C, more preferably at least 120°C, still more preferably at least 130°C, still more preferably at least 140°C, even more preferably at least 150°C, most preferably at least 160°C, and in particular at least 170°C; and / or - at most 200°C, more preferably at most 195°C, still more preferably at most 190°C, still more preferably at most 185°C, even more preferably at most 180°C, most preferably at most 175°C, and in particular at most 170°C.
24. A composition according to any preceding claim which is dry to the touch and / or non-tacky at 23°C.
25. The composition according to any of the preceding claims, wherein the content of epoxy resin is at most 10 wt.-%, preferably at most 7.5 wt.-%, in each case relative to the total weight of the composition.
26. The composition of any of the preceding claims, wherein the first ethylene copolymer comprises or consists essentially of: One or more ethylene / butyl acrylate copolymers.
27. The composition according to any of the preceding claims, wherein the content of the first ethylene copolymer is in the range of 45±40 wt.-%, preferably 45±35 wt.-%, more preferably 45±30 wt.-%, still more preferably 45±25 wt.-%, still more preferably 45±20 wt.-%, even more preferably 45±15 wt.-%, most preferably 45±10 wt.-% and in particular 45±5.0 wt.-%, in each case relative to the total weight of the composition.
28. The composition according to any of the preceding claims, wherein at least 40 wt.-%, preferably at least 45 wt.-%, of the first ethylene copolymer, relative to the total content of the first ethylene copolymer, has a melt index according to ISO 1133 (190° C. / 2.16 kg) below 50 g / 10 min.
29. The composition according to any of the preceding claims, wherein the first ethylene copolymer does not comprise any copolymer having a melt index according to ISO 1133 (190°C / 2.16 kg) higher than 450 g / 10 min, preferably higher than 350 g / 10 min.
30. The composition of any of the preceding claims, wherein the first ethylene copolymer comprises or consists essentially of a mixture of: - ethylene / butyl acrylate copolymer A, whose melt index according to ISO 1133 (190° C. / 2.16 kg) is in the range of 300±275 g / 10 min, preferably 300±250 g / 10 min, more preferably 300±225 g / 10 min, still more preferably 300±200 g / 10 min, still more preferably 300±175 g / 10 min, even more preferably 300±150 g / 10 min, most preferably 300±100 g / 10 min and in particular 300±50 g / 10 min; and - ethylene / butyl acrylate copolymer B, whose melt index according to ISO 1133 (190°C / 2.16 kg) is in the range of 40±37.5 g / 10 min, preferably 40±35 g / 10 min, more preferably 40±30 g / 10 min, still more preferably 40±25 g / 10 min, still more preferably 40±20 g / 10 min, even more preferably 40±15 g / 10 min, most preferably 40±10 g / 10 min and in particular 40±5.0 g / 10 min.
31. The composition of any of the preceding claims, wherein the first ethylene copolymer comprises or consists essentially of a mixture of: - ethylene / butyl acrylate copolymer A, whose content is in the range of 22.5±20.0 wt.-%, preferably 22.5±17.5 wt.-%, more preferably 22.5±15.0 wt.-%, still more preferably 22.5±12.5 wt.-%, still more preferably 22.5±10.0 wt.-%, even more preferably 22.5±7.5 wt.-%, most preferably 22.5±5.0 wt.-% and in particular 22.5±2.5 wt.-%, in each case relative to the total weight of the composition; and - ethylene / butyl acrylate copolymer B, whose content is in the range of 22.5±20.0 wt.-%, preferably 22.5±17.5 wt.-%, more preferably 22.5±15.0 wt.-%, still more preferably 22.5±12.5 wt.-%, still more preferably 22.5±10.0 wt.-%, even more preferably 22.5±7.5 wt.-%, most preferably 22.5±5.0 wt.-% and in particular 22.5±2.5 wt.-%, in each case relative to the total weight of the composition.
32. The composition of any of the preceding claims, wherein the second ethylene copolymer comprises or consists essentially of: One or more ethylene / vinyl acetate copolymers.
33. The composition according to any of the preceding claims, wherein the content of the second ethylene copolymer is in the range of 7.5±7.0 wt.-%, preferably 7.5±6.5 wt.-%, more preferably 7.5±6.0 wt.-%, still more preferably 7.5±5.5 wt.-%, still more preferably 7.5±5.0 wt.-%, even more preferably 7.5±4.5 wt.-%, most preferably 7.5±4.0 wt.-% and in particular 7.5±3.5 wt.-%, in each case relative to the total weight of the composition.
34. The composition according to any of the preceding claims, wherein at least 40 wt.-%, preferably at least 45 wt.-%, of the second ethylene copolymer, relative to the total content of the second ethylene copolymer, has a melt index according to ISO 1133 (190° C. / 2.16 kg) below 50 g / 10 min.
35. The composition according to any of the preceding claims, wherein the second ethylene copolymer does not comprise any copolymer having a melt index according to ISO 1133 (190°C / 2.16 kg) higher than 1000 g / min, preferably higher than 900 g / 10 min.
36. A composition according to any of the preceding claims, wherein the second ethylene copolymer comprises or consists essentially of a mixture of: - ethylene / vinyl acetate copolymer C having a melt index according to ISO 1133 (190° C. / 2.16 kg) in the range of 800±750 g / 10 min, preferably 800±700 g / 10 min, more preferably 800±600 g / 10 min, still more preferably 800±500 g / 10 min, still more preferably 800±400 g / 10 min, even more preferably 800±300 g / 10 min, most preferably 800±200 g / 10 min and in particular 800±100 g / 10 min; and - ethylene / vinyl acetate copolymer D, whose melt index according to ISO 1133 (190°C / 2.16 kg) is in the range of 6.5±5.0 g / 10 min, preferably 6.5±4.5 g / 10 min, more preferably 6.5±30 g / 4.0 min, still more preferably 6.5±3.5 g / 10 min, still more preferably 6.5±3.0 g / 10 min, even more preferably 6.5±2.5 g / 10 min, most preferably 6.5±2.0 g / 10 min and in particular 6.5±1.5 g / 10 min.
37. A composition according to any of the preceding claims, wherein the second ethylene copolymer comprises or consists essentially of a mixture of: - ethylene / vinyl acetate copolymer C, whose content is in the range of 3.75±3.50 wt.-%, preferably 3.75±3.25 wt.-%, more preferably 3.75±3.00 wt.-%, still more preferably 3.75±2.50 wt.-%, still more preferably 3.75±2.00 wt.-%, even more preferably 3.75±1.50 wt.-%, most preferably 3.75±1.00 wt.-% and in particular 3.75±0.50 wt.-%, in each case relative to the total weight of the composition; and - ethylene / vinyl acetate copolymer D, whose content is in the range of 3.75±3.50 wt.-%, preferably 3.75±3.25 wt.-%, more preferably 3.75±3.00 wt.-%, still more preferably 3.75±2.50 wt.-%, still more preferably 3.75±2.00 wt.-%, even more preferably 3.75±1.50 wt.-%, most preferably 3.75±1.00 wt.-% and in particular 3.75±0.50 wt.-%, in each case relative to the total weight of the composition.
38. A composition according to any of the preceding claims, wherein the ethylene terpolymer comprises or consists essentially of: One or more reactive ethylene terpolymers.
39. A composition according to any of the preceding claims, wherein the ethylene terpolymer comprises or consists essentially of: One or more reactive elastomeric ethylene terpolymers.
40. The composition of any of the preceding claims, wherein the ethylene terpolymer comprises or consists essentially of: One or more butyl acrylate / glycidyl methacrylate / ethylene terpolymers.
41. A composition according to any of the preceding claims, wherein the content of ethylene terpolymer is in the range of 4.5±4.0 wt.-%, preferably 4.5±3.5 wt.-%, more preferably 4.5±3.0 wt.-%, still more preferably 4.5±2.5 wt.-%, still more preferably 4.5±2.0 wt.-%, even more preferably 4.5±1.5 wt.-%, most preferably 4.5±1.0 wt.-% and in particular 4.5±0.5 wt.-%, in each case relative to the total weight of the composition.
42. The composition according to any of the preceding claims, wherein at least 40 wt.-%, preferably at least 45 wt.-%, of the ethylene terpolymer, relative to the total content of the ethylene terpolymer, has a melt index according to ISO 1133 (190° C. / 2.16 kg) below 50 g / 10 min.
43. The composition according to any of the preceding claims, wherein the ethylene terpolymer does not include any terpolymer having a melt index according to ISO 1133 (190°C / 2.16 kg) higher than 50 g / 10 min, preferably higher than 10 g / 10 min.
44. A composition according to any of the preceding claims, wherein the ethylene terpolymer has a melt index according to ISO 1133 (190°C / 2.16 kg) in the range of 8.0±5.0 g / 10 min, preferably 8.0±4.5 g / 10 min, more preferably 8.0±30 g / 4.0 min, still more preferably 8.0±3.5 g / 10 min, still more preferably 8.0±3.0 g / 10 min, even more preferably 8.0±2.5 g / 10 min, most preferably 8.0±2.0 g / 10 min, and in particular 8.0±1.5 g / 10 min.
45. A composition according to any of the preceding claims, wherein the tackifier comprises or consists essentially of: One or more hydrocarbon tackifier resins.
46. A composition according to any of the preceding claims, wherein the blowing agent comprises or consists essentially of: One or more chemical blowing agents.
47. A composition according to any of the preceding claims, wherein the blowing agent comprises or consists essentially of: Azodicarbonamide.
48. A composition according to any of the preceding claims, wherein the rheology modifier comprises or consists essentially of: One or more thixotropic rheology modifiers.
49. A composition according to any of the preceding claims, wherein the blowing agent promoter comprises or consists essentially of: Zinc oxide.
50. A composition according to any of the preceding claims, wherein the free radical polymerization initiator comprises or consists essentially of: One or more organic peroxides.
51. A composition according to any of the preceding claims, wherein the free radical polymerization initiator comprises or consists essentially of: (i) a first organic peroxide selected from dibenzoyl peroxide; and (ii) a second organic peroxide selected from 1,1'-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane peroxide.
52. A composition according to any of the preceding claims, additionally comprising one or more reactive diluents; preferably selected from epoxy-containing diluents and compounds deriving their reactivity from functional groups other than epoxides (non-epoxy reactive diluents).
53. A composition according to any of the preceding claims comprising one or more monofunctional, difunctional or multifunctional epoxy reactive diluents selected from: (i) unsaturated, branched or unbranched, cyclic or open chain, aliphatic or aromatic C4-C 30 Oxides of hydrocarbons, For example, octane oxide, butadiene dioxide, cyclohexene epoxide compounds, alloocimene dioxide, limonene dioxide, vinylcyclohexane dioxide, styrene oxide, divinylbenzene dioxide; (ii) a monobasic saturated or unsaturated, branched or unbranched, cyclic or open-chain C4-C 30 Glycidyl ethers of alcohols, such as butanol glycidyl ether, hexanol glycidyl ether, 2-ethylhexanol glycidyl ether, allyl glycidyl ether, tetrahydrofurfuryl glycidyl ether, and furfuryl glycidyl ether, trimethoxysilyl glycidyl ether; (iii) dibasic saturated or unsaturated, branched or unbranched, cyclic or open-chain C2-C 30 Glycidyl ethers of alcohols, for example ethylene glycol glycidyl ether, butanediol glycidyl ether, hexanediol glycidyl ether, octanediol glycidyl ether, diethylene glycol diglycidyl ether, cyclohexanedimethanol diglycidyl ether, neopentyl glycol diglycidyl ether; (iv) glycidyl ethers of tri- or polyhydric, saturated or unsaturated, branched or unbranched, cyclic or open-chain alcohols, for example epoxidized castor oil, epoxidized trimethylolpropane, triglycidyl ether of trimethylolpropane, epoxidized pentaerythritol, or polyglycidyl ethers of aliphatic polyols, for example sorbitol, glycerol, trimethylolpropane, diglycidyl ether of cyclohexanedimethanol; (v) Glycidyl ethers of phenolic compounds and aniline compounds, such as phenyl glycidyl ether, monoglycidyl ethers of alkyl- and alkenyl-substituted phenols, cresyl glycidyl ether, diglycidyl ether of resorcinol, p-tert-butylphenyl glycidyl ether, nonylphenol glycidyl ether, 3-n-pentadecenyl-glycidyl ether (from cashew nut shell liquid), epoxidized cashew nut shell liquid, N,N-diglycidyl aniline; (vi) epoxide amines, for example N,N-diglycidylcyclohexylamine; (vii) epoxidized mono- or dicarboxylic acids, for example glycidyl neodecanoate, glycidyl methacrylate, glycidyl benzoate, diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl hexahydrophthalate, glycidyl esters of tertiary carboxylic acids, diglycidyl esters of dimerized fatty acids; and (viii) Epoxidized di- or tri-hydric, low to high molecular weight polyether polyols, for example polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether.
54. A composition according to any preceding claim which is a paste having a flowable viscosity at a temperature of 15°C such that it is pumpable.
55. A composition according to any of the preceding claims, having a viscosity of at most 900 Pa·s, preferably at most 800 Pa·s, more preferably at most 700 Pa·s, still more preferably at most 600 Pa·s, still more preferably at most 500 Pa·s, even more preferably at most 400 Pa·s, most preferably at most 300 Pa·s, and in particular at most 200 Pa·s, as measured by a rotational viscometer at a temperature of 15°C.
56. A composition according to any of the preceding claims, having a viscosity in the range of 200 to 800 Pa·s, preferably 250 to 400 Pa·s, measured by a rotational viscometer at a temperature of 15°C.
57. A composition according to any of the preceding claims, having a viscosity of at least 3 Pa·s, preferably at least 5 Pa·s, more preferably at least 7 Pa·s, still more preferably at least 9 Pa·s, still more preferably at least 11 Pa·s, even more preferably at least 13 Pa·s, most preferably at least 15 Pa·s, and in particular at least 17 Pa·s, as measured by a rotational viscometer at a temperature of 60°C; preferably in the range of 5 to 20 Pa·s.
58. A composition according to any of the preceding claims, which can be heated to a first elevated intermediate temperature T1 and a second elevated intermediate temperature T2 that is 40°C higher than T1 (i.e. T2 = T1 + 40°C); wherein T2 and preferably also T1 are above room temperature (i.e. 23°C); wherein both T1 and T2 are below the curing temperature and below the activation temperature of an optionally present blowing agent; wherein at T1, the composition has a viscosity ν1; and wherein at T2, the composition has a viscosity ν2; wherein the viscosity ratio ν1:ν2 is at least 5, preferably at least 10, more preferably at least 15, still more preferably at least 20, still more preferably at least 25, even more preferably at least 30, most preferably at least 35, and in particular at least 40; wherein T2 is preferably 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C.
59. A composition according to any of the preceding claims, which can be heated to a first elevated intermediate temperature T1 and a second elevated intermediate temperature T2 that is 30°C higher than T1 (i.e. T2 = T1 + 30°C); wherein T2 and preferably also T1 are above room temperature (i.e. 23°C); wherein both T1 and T2 are below the curing temperature and below the activation temperature of an optionally present blowing agent; wherein at T1, the composition has a viscosity ν1; and wherein at T2, the composition has a viscosity ν2; wherein the viscosity ratio ν1:ν2 is at least 5, preferably at least 10, more preferably at least 15, even more preferably at least 20, still more preferably at least 25, even more preferably at least 30, most preferably at least 35, and in particular at least 40; wherein T2 is preferably 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C.
60. A composition according to any of the preceding claims, which can be heated to a first elevated intermediate temperature T1 and a second elevated intermediate temperature T2 that is 20°C higher than T1 (i.e. T2 = T1 + 20°C); wherein T2 and preferably also T1 are above room temperature (i.e. 23°C); wherein both T1 and T2 are below the curing temperature and below the activation temperature of an optionally present blowing agent; wherein at T1, the composition has a viscosity ν1; and wherein at T2, the composition has a viscosity ν2; wherein the viscosity ratio ν1:ν2 is at least 5, preferably at least 10, more preferably at least 15, even more preferably at least 20, still more preferably at least 25, even more preferably at least 30, most preferably at least 35, and in particular at least 40; wherein T2 is preferably 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C.
61. A composition according to any of the preceding claims, which can be heated to a first elevated intermediate temperature T1 and a second elevated intermediate temperature T2 that is 10°C higher than T1 (i.e. T2 = T1 + 10°C); wherein T2 and preferably also T1 are above room temperature (i.e. 23°C); wherein both T1 and T2 are below the curing temperature and below the activation temperature of an optionally present blowing agent; wherein at T1, the composition has a viscosity ν1; and wherein at T2, the composition has a viscosity ν2; wherein the viscosity ratio ν1:ν2 is at least 5, preferably at least 10, more preferably at least 15, even more preferably at least 20, still more preferably at least 25, even more preferably at least 30, most preferably at least 35, and in particular at least 40; wherein T2 is preferably 50°C, or 60°C, or 70°C, or 80°C, or 90°C, or 100°C, or 110°C.
62. A composition according to any preceding claim which passes a wash-off test involving the following steps: (a) applying beads of the composition to an oil loading of 1.5 g / m 2 (Preferred PL3802-39S, 1.5g / m 2 =0.12g) on the surface of a stainless steel specimen (preferably a hot-dip galvanized steel plate (DX54D+Z100, 200×40mm)), wherein the steel plate is used as a substrate without a counter substrate (top plate); (b) without pre-curing, the sample prepared in this way is placed in an immersion fixture and dropped unhindered from a height of 20cm into a tank filled with pure water at room temperature (23°C); (c) the sample is mounted on an agitator in a second tank filled with pure water preheated to 55°C; (d) the sample is stirred at a speed of 60rpm (0.82m / s) for 3 minutes; (e) the sample is removed and visually inspected, wherein the adhesive composition passes the wash-off resistance test when no significant change of the adhesive composition is detected.
63. A composition according to any of the preceding claims which passes the wash-off test according to BMW standard AA-0044 from January 2018; preferably involving the following steps: (a) applying beads of the composition to an oily surface with an oil loading of 1.5 g / m 2 (Preferred PL3802-39S, 1.5g / m 2 =0.12g) on the surface of a stainless steel specimen (preferably a hot-dip galvanized steel plate (DX54D+Z100, 200×40mm)), wherein the steel plate is used as a substrate without a counter substrate (top plate); (b) without pre-curing, the sample prepared in this way is placed in an immersion fixture and dropped unhindered from a height of 20cm into a tank filled with pure water at room temperature (23°C); (c) the sample is mounted on an agitator in a second tank filled with pure water preheated to 60°C; (d) the sample is stirred at a speed of 140rpm (1.47m / s) for 3 minutes; (e) the sample is removed and visually inspected, wherein the adhesive composition passes the wash-off resistance test when no significant change of the adhesive composition is detected.
64. A motor vehicle assembly comprising: -Transportation components and - Extruded beads of a curable polymer composition according to any of the preceding claims on the surface of the vehicle component.
65. The motor vehicle assembly of claim 64, wherein the extruded beads pass a wash-off test involving the following steps: (a) applying beads of the composition to an oil loading of 1.5 g / m 2 (Preferred PL3802-39S, 1.5g / m 2 =0.12g) on the surface of a stainless steel specimen (preferably a hot-dip galvanized steel plate (DX54D+Z100, 200×40mm)), wherein the steel plate is used as a substrate without a counter substrate (top plate); (b) without pre-curing, the sample prepared in this way is placed in an immersion fixture and dropped unhindered from a height of 20cm into a tank filled with pure water at room temperature (23°C); (c) the sample is mounted on an agitator in a second tank filled with pure water preheated to 55°C; (d) the sample is stirred at a speed of 60rpm (0.82m / s) for 3 minutes; (e) the sample is removed and visually inspected, wherein the adhesive composition passes the wash-off resistance test when no significant change of the adhesive composition is detected.
66. A motor vehicle assembly according to claim 64 or 65, wherein the extruded beads pass the wash-off test according to BMW standard AA-0044 from January 2018; preferably involving the following steps: (a) applying beads of the composition to an oil load of 1.5 g / m 2 (Preferred PL3802-39S, 1.5g / m 2 =0.12g) on the surface of a stainless steel specimen (preferably a hot-dip galvanized steel plate (DX54D+Z100, 200×40mm)), wherein the steel plate is used as a substrate without a counter substrate (top plate); (b) without pre-curing, the sample prepared in this way is placed in an immersion fixture and dropped unhindered from a height of 20cm into a tank filled with pure water at room temperature (23°C); (c) the sample is mounted on an agitator in a second tank filled with pure water preheated to 60°C; (d) the sample is stirred at a speed of 140rpm (1.47m / s) for 3 minutes; (e) the sample is removed and visually inspected, wherein the adhesive composition passes the wash-off resistance test when no significant change of the adhesive composition is detected.
67. A motor vehicle assembly as claimed in any of claims 64 to 66 wherein the extruded beads exhibit resiliency in response to loads encountered during manufacturing operations.
68. A motor vehicle assembly according to any of claims 64 to 67, wherein the vehicle component is selected from the group consisting of a vehicle hood, a vehicle roof, a roof bow, a vehicle door, a door beam, a tubular frame member, a vehicle bumper, a front fender flare, a vehicle door sill, a vehicle pillar such as an A-pillar (preferably a lower or upper outer section thereof) or a B-pillar (preferably a lower or upper outer section thereof), a pillar closure, a vehicle suspension component, a vehicle support member, a side impact beam, a reinforcement bar, a vehicle skin, a vehicle hood, a vehicle trunk, a tail lamp, a fuel filler, a battery housing, a battery support or any combination thereof.
69. A motor vehicle assembly according to any of claims 64 to 68, wherein the extruded beads have the following: (i) an extrusion axis along the direction of movement of the die relative to the substrate to which the beads are applied; (ii) an average cross-sectional area (measured in a section perpendicular to the extrusion axis) of at least 0.1 cm 2 , preferably at least 1.0 cm 2 , more preferably at least 2.0 cm 2 ; and up to 10cm 2 , preferably at most 8.0 cm 2 , more preferably at most 6.0 cm 2 , and still more preferably at most 4.0 cm 2 ; (iii) the cross-sectional profile along the extrusion axis is circular, elliptical, hemispherical, rectangular, polygonal, has multiple convex corners, or any combination thereof; and / or (iv) a length of at least 1.0 cm, preferably at least 5.0 cm, more preferably at least 10 cm, and still more preferably at least 20 cm; and at most 1000 cm, preferably at most 750 cm, more preferably at most 500 cm, still more preferably at most 300 cm, and still more preferably at most 100 cm.
70. A method of producing a motor vehicle assembly according to any of claims 64 to 69, said method comprising the steps of: (a) providing the vehicle assembly; and (b) Extruding beads of a curable polymer composition according to any of claims 1 to 57 by an extrusion device and directly onto the surface of the vehicle component.
71. The method of claim 70, wherein the temperature of a surface of the vehicle component is controlled.
72. A method according to claim 70 or 71, wherein the temperature of the surface of the vehicle component is at most 65°C, preferably at most 60°C, more preferably at most 55°C, even more preferably at most 50°C, still more preferably at most 45°C, even more preferably at most 40°C, most preferably at most 35°C, and in particular at most 30°C when the beads contact the surface of the vehicle component throughout the duration of extrusion.
73. A method according to any of claims 70 to 72, wherein the surface of the vehicle component provided in step (a) is oily.
74. A method according to any of claims 70 to 73, wherein step (b) is performed robotically.
75. A method according to any of claims 70 to 74, wherein the extrusion in step (b) is carried out at a temperature of the curable polymer composition that is ambient temperature (extrusion temperature).
76. A method according to any of claims 70 to 74, wherein in step (b) the extrusion is carried out at a temperature of the curable polymer composition which is above ambient temperature (extrusion temperature).
77. The method according to any of claims 70 to 76, wherein in step (b) the extrusion is carried out at a temperature of the curable polymer composition (extrusion temperature) of at most 65°C, preferably at most 60°C, more preferably at most 55°C, still more preferably at most 50°C, still more preferably at most 45°C, even more preferably at most 40°C, most preferably at most 35°C, and in particular at most 30°C.
78. A method according to any of claims 70 to 76, wherein step (b) comprises extruding multiple layers of beads, preferably extruding multiple layers of beads on top of each other.
79. The method of any of claims 70 to 76, wherein step (b) comprises the following sub-steps: (b1) extruding beads of the curable polymer composition through an extrusion device and directly onto a surface of the vehicle component (optionally extruding the beads into a cavity defined by an interior surface of the component); (b2) extruding a second bead of the curable polymer composition through the extrusion device and directly onto the surface of the bead, the bead being an auxiliary directly extruded onto the surface of the vehicle component; (b3) optionally, extruding a third bead of the curable polymer composition through the extrusion device and directly onto the surface of the second bead; (b4) optionally, extruding fourth beads of the curable polymer composition through the extrusion device and directly onto the surface of the third beads; and (b5) Optionally, extruding fifth beads of the curable polymer composition through the extrusion device and directly onto the surface of the fourth beads.
80. The method according to any of claims 70 to 79, comprising the additional step of: (c) immersing the vehicle component having the extruded beads on its surface into a bath of liquid coating fluid.
81. A method according to claim 80, wherein after the extrusion in step (b) and until the immersion in step (c), the temperature of the motor vehicle assembly is maintained at a temperature of at most 65°C, preferably at most 60°C, more preferably at most 55°C, even more preferably at most 50°C, still more preferably at most 45°C, even more preferably at most 40°C, most preferably at most 35°C, and in particular at most 30°C.
82. A method according to claim 80 or 81 , without any step of pre-curing (pre-baking) the motor vehicle assembly or the extruded beads of curable polymer composition prior to the immersion in step (c).
83. A method according to any of claims 80 to 82, without any step of applying a counter substrate to the motor vehicle assembly or the extruded beads of curable polymer composition prior to the immersing in step (c).
84. The method according to any of claims 70 to 83, comprising the additional step of: (d) heating the motor vehicle assembly or the extruded beads of the curable polymer composition to a temperature that is above the curing temperature of the curable polymer composition to cause curing; and optionally above the activation temperature of an optionally present blowing agent to cause volume expansion.
85. A method according to any of claims 70 to 84, wherein during step (d) the curable polymer composition on the surface of the vehicle component is bonded to the surface of a counter substrate.
86. The method of claim 85, wherein during step (d) the curable polymer composition on the surface of the vehicle component expands to contact the surface of the opposing substrate.
87. A method according to claim 85 or 86, wherein before performing step (d), the gap between the surface of the vehicle component and the surface of the opposing substrate, at least in a local area, is less than 70 mm, preferably less than 50 mm, and more preferably less than 20 mm; preferably at most 18 mm, more preferably at most 16 mm, even more preferably at most 14 mm, still more preferably at most 12 mm, even more preferably at most 10 mm, most preferably at most 8 mm, and in particular at most 6 mm.
88. Use of a curable polymer composition according to any of claims 1 to 63, preferably in a method according to any of claims 70 to 85, for producing a motor vehicle assembly according to any of claims 64 to 69.
Citation Information
Patent Citations
Method and apparatus for applying flowable materials like polyurethane or epoxy resin after pretreating the surface with plasma or primer
EP1331080A2
Pumpable and thermally expandable filler compositions
EP3281970A1
Polymer-phyllosilicate nanocomposites and their preparation
US20040214921A1
Method and apparatus for applying flowable materials
US20060127584A1
Polymer exfoliated phyllosilicate nanocomposite compositions and a process for the preparation thereof
US20070191527A1